Dental Composition
By using a cyclic amid monomer in the dental composition and utilizing its ring-opening reaction and free radiation polymerization characteristics, the problem of increasing stress during the polymerization process is solved, and a significant reduction of polymerization stress and maintenance of mechanical properties is achieved.
Patent Information
- Application Number
- JP2024533900
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-06
- Filing Date
- 2022-11-01
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-11-01
AI Technical Summary
During the polymerization process, the increase in stress caused by volume reduction in dental composite materials leads to problems such as caries, reduced durability, shortened service life and residual internal stress.
Polymerizable dental compositions containing cyclic acyl imid monomers are employed that reduce polymerization stress by ring opening reaction and free radiation during polymerization and reduce post-coagulation stress by delaying gelation points.
The polymerization stress is significantly reduced without damaging the mechanical properties of the polymer, extends the service life of the dental composition and reduces residual stress.
Smart Images

Figure 0007660768000001 
Figure 0007660768000002 
Figure 0007660768000003
Abstract
Description
[Technical field]
[0001] Polymerizable dental compositions that include addition-cleavage agents are described, for example, in US Pat. Nos. 9,056,043 and 9,907,733. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0002] Polymerization-based stress is caused by the shrinkage of materials during curing. This volumetric shrinkage leads to many problems, including cracking, reduced durability, shortened lifespan, and residual internal stress. Therefore, reducing polymerization shrinkage and shrinkage stress is of great interest to the industry.
[0003] Various methods have been identified to reduce stress (e.g., cleavable crosslinkers, slowing the cure to delay the transition of the material from viscous to elastic, and / or adding monomers that cleave and then add to the polymer network during polymerization). Certain monomers that cleave and add during cure have been developed that show remarkable performance in reducing shrinkage stress in free radical cured dental composites and structural adhesives. However, additional monomers that can contribute to further reduction of stress in dental composites are desirable.
[0004] As used herein, "dental composition" refers to a material, optionally including a filler, that can be adhered or bonded to an oral surface. Hardenable dental compositions can be used to bond dental articles to tooth structures, can be used to form coatings (e.g., sealants or varnishes) on tooth surfaces, can be used as restoratives that are placed directly in the oral cavity and hardened in place, or, alternatively, can be used to create prostheses outside the oral cavity and then bonded in the oral cavity.
[0005] Hardenable dental compositions include, for example, adhesives (e.g., dental adhesives and / or orthodontic adhesives), cements (e.g., resin-modified glass ionomer cements and / or orthodontic cements), coatings such as primers (e.g., orthodontic primers), liners (applied to the base of cavities to reduce tooth sensitivity), sealants (e.g., pit and fissure) and varnishes, as well as resin restoratives (also called direct composites) such as dental fillings, and articles for crowns, bridges, and dental implants. Highly filled dental compositions are also used for mill blanks from which crowns can be milled. Dental cements are somewhat less filled and less viscous materials than composites, and typically act as bonding agents for additional materials such as inlays, onlays, or as the filling material itself when applied and hardened in layers. Dental cements are also used to permanently bond dental restorations such as crowns or bridges to tooth surfaces or implant abutments.
[0006] As used herein, "dental article" refers to an article that can be adhered (e.g., bonded) to a tooth structure or a dental implant. Dental articles include, for example, crowns, bridges, veneers, inlays, onlays, fillings, orthodontic appliances and devices. "Addition-cleavage agent" refers to a monomer that contains a cleavable ethylenically unsaturated group (i.e., a group that cleaves during cure by homolytic junction scission (including ring opening)) and may have at least one additional free radically polymerizable group within its structure (e.g., a (meth)acrylate group); "Orthodontic appliance" refers to any device intended to be bonded to tooth structure, including, but not limited to, orthodontic brackets, buccal tubes, lingual retainers, orthodontic bands, bite openers, buttons, and cleats. The appliance has a base for receiving an adhesive, which may be a flange made from metal, plastic, ceramic, or a combination thereof. Alternatively, the base may be a custom base formed from hardened adhesive layer(s) (i.e., single or multi-layer adhesive), "Oral surfaces" refers to soft or hard surfaces in the oral environment. Hard surfaces typically include, for example, tooth structures, including natural and artificial tooth surfaces, bone, etc. "Cureable" and "curable" refer to a material or composition that can be cured (e.g., polymerized or crosslinked) by heating to induce polymerization and / or crosslinking, by irradiating with actinic radiation to induce polymerization and / or crosslinking, and / or by mixing one or more components to induce polymerization and / or crosslinking. "Mixing" can be performed, for example, by combining two or more parts to form a homogenous composition. Alternatively, two or more parts can be provided as separate layers that mix (e.g., spontaneously or upon application of shear stress) at an interface to initiate polymerization, "Cured" refers to a material or composition that is at least partially cured (e.g., polymerized or crosslinked); "Hardening agent" refers to an agent that initiates the hardening of a resin. Hardening agents may include, for example, a polymerization initiator system, a photoinitiator system, a thermal initiator, and / or a redox initiator system; "(meth)acrylate" is shorthand for acrylate, methacrylate, or a combination thereof, "(meth)acrylic" is shorthand for acrylic, methacrylic, or a combination thereof, and "(meth)acrylic" is shorthand for acrylic, methacrylic, or a combination thereof; "Acryloyl" is used in a general sense to refer not only to derivatives of acrylic acid but also to the amine and alcohol derivatives, respectively; "(Meth)acryloyl" includes both acryloyl and methacryloyl groups, i.e., both esters and amides; "Alkyl" includes straight-chain, branched-chain, and cyclic alkyl groups, and includes both unsubstituted and substituted alkyl groups. Unless otherwise specified, alkyl groups typically contain 1 to 20 carbon atoms. Examples of "alkyl" as used herein include, but are not limited to, methyl, ethyl, n-propyl, n-butyl, n-pentyl, isobutyl, t-butyl, isopropyl, n-octyl, n-heptyl, ethylhexyl, cyclopentyl, cyclohexyl, cycloheptyl, adamantyl, and norbornyl. Unless otherwise specified, alkyl groups may be mono- or polyvalent, i.e., monovalent alkyl or polyvalent alkylene; "Heteroalkyl" includes straight-chain, branched-chain, and cyclic alkyl groups having one or more heteroatoms independently selected from S, O, and N, and includes both unsubstituted and substituted alkyl groups. Unless otherwise specified, heteroalkyl groups typically contain 1 to 20 carbon atoms. "Heteroalkyl" is a subset of "hydrocarbyl containing one or more S, N, O, P, or Si atoms" described below. Examples of "heteroalkyl" as used herein include, but are not limited to, methoxy, ethoxy, propoxy, 3,6-dioxaheptyl, 3-(trimethylsilyl)-propyl, 4-dimethylaminobutyl, and the like. Unless otherwise specified, heteroalkyl groups may be mono- or polyvalent, i.e., monovalent heteroalkyl or polyvalent heteroalkylene; "Aryl" is an aromatic group containing 5 to 18 ring atoms and may contain any fused rings that may be saturated, unsaturated, or aromatic. Examples of aryl groups include phenyl, naphthyl, biphenyl, phenanthryl, and anthracyl. Heteroaryl is an aryl containing 1 to 3 heteroatoms such as nitrogen, oxygen, or sulfur and may contain fused rings. Some examples of heteroaryl groups are pyridyl, furanyl, pyrrolyl, thienyl, thiazolyl, oxazolyl, imidazolyl, indolyl, benzofuranyl, and benzthiazolyl. Unless otherwise specified, aryl and heteroaryl groups may be mono- or polyvalent, i.e., monovalent aryl or polyvalent arylene; As used herein, "a," "an," "the," "at least one," and "one or more" are used interchangeably.
[0007] Also herein, the recitations of numerical ranges by endpoints include all numbers subsumed within that range (eg, 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).
[0008] In some embodiments, the present disclosure relates to polymerizable dental compositions that may include a hardenable component that includes: (i) an addition-cleavage agent that includes a cyclic imide monomer; (ii) an addition-cleavage agent that optionally includes in its structure a cleavable ethylenically unsaturated group having at least one free radically polymerizable group (not including those that include a cyclic imide monomer); and (iii) at least one ethylenically unsaturated monomer or oligomer.
[0009] In general, dental composites containing the cyclic imide monomers of the present invention as stress-reducing additives have been found to significantly reduce polymerization-based stresses in free-radically cured dental composites (without degrading the mechanical properties of the cured composition) as compared to known stress-reducing monomers. Additionally, dental composites containing both the cyclic imide monomers of the present invention and certain known monomers that cleave during curing (sometimes referred to herein as addition-cleavage agents) have been found to outperform composites containing either the cyclic imide monomers of the present invention or the certain addition-cleavage agents alone.
[0010] In some embodiments, the hardenable components of the present disclosure may include an addition-cleavage agent that includes one or more cyclic imide monomers that include an α,β-unsaturated carbonyl. In some embodiments, the cyclic imide monomers can act as addition-cleavage agents in the polymerizable composition (e.g., free radically polymerizable composition).
[0011] In some embodiments, the cyclic imide monomer may include at least one imide group consisting of two acyl groups attached to a nitrogen. The cyclic imide monomers described herein may further include alpha, beta-unsaturation (α,β-unsaturation), i.e., a π bond between the α and β carbons adjacent to the carbonyl group. In some embodiments, the cyclic imide monomer may further include a quaternary carbon atom at the γ position (referred to herein as a γ-quaternary carbon atom) (i.e., three carbon atoms away from the carbon atom of the carbonyl group adjacent to the α,β-unsaturation). It should be understood that in some embodiments, the presence of a quaternary carbon atom at the γ position is the primary driver of the ring-opening step (discussed in more detail below).
[0012] Cyclic imide monomers can be prepared by reacting a dicarboxylic acid containing an α,β-unsaturated carbonyl with a dehydrating agent such as acetic anhydride to form a cyclic compound containing an anhydride group and an α,β-unsaturated carbonyl, and reacting the anhydride group with a (e.g., primary) amine compound.
[0013] In some embodiments, the dicarboxylic acid comprises at least three consecutive carbon atoms with an α,β-unsaturated carbonyl between the acid groups. Thus, the imide group and the pendant α,β-unsaturation are typically present in a heterocyclic molecule, the ring of which comprises at least six covalently bonded atoms. In other words, the cyclic imide monomers described herein comprise one or more heterocyclic rings, the ring(s) of which comprise six or more covalently bonded atoms in the heterocyclic ring, and the heterocyclic ring comprises both an imide group and an α,β-unsaturated carbonyl.
[0014] In some embodiments, representative dicarboxylic acids containing an α,β-unsaturated carbonyl are represented as follows:
[0015] [ka] 2,2-Dimethyl-4-methylidenepentanedioic acid (also written as 2,4-biscarboxy-4-methylpent-1-ene or 2,2-dimethyl-4-methylene glutaric acid).
[0016] In some embodiments, such dicarboxylic acids are used to prepare cyclic imide monomers that contain a single ring. The cyclic imide monomers may have the following structure:
[0017] [ka] wherein L is a covalent bond or an organic linking group, Y is an alkyl, aryl, hydroxyl, carboxylic acid, or an ethylenically unsaturated group, and R1 and R2 are independently alkyl groups.
[0018] In some embodiments, R1 and R2 are independently a C1-C18 alkyl group, a C1-C16 alkyl group, a C1-C10 alkyl group, or a C1-C4 alkyl group (e.g., methyl, ethyl, propyl, or butyl). In some embodiments, R1 and R2 are alkyl substituents such that the cyclic imide monomer undergoes ring opening during polymerization, thereby forming a radical.
[0019] L typically comprises a (hetero)alkylene, a (hetero)arylene, or a combination thereof. In some embodiments, the alkylene or arylene linking group (i.e., L) may contain a heteroatom, such as oxygen. For example, L may contain one or more ester moieties, one or more urethane moieties, and / or one or more pendant hydroxyl groups.
[0020] In some embodiments, 2,2-dimethyl-4-methylene glutaric anhydride is used to prepare a cyclic imide monomer containing two rings, or in other words, a cyclic bis-imide. The cyclic bis-imide monomer may have the following structure:
[0021] [ka] where R is an organic linking group; R1 and R2 are independently substituents as described above.
[0022] R typically comprises a (hetero)alkylene, a (hetero)arylene, or a combination thereof.
[0023] In some embodiments, the alkylene or arylene linking group (i.e., R) may contain heteroatoms such as oxygen or nitrogen. For example, R may contain one or more ester moieties, one or more urethane moieties, and / or one or more pendant hydroxyl groups. R may optionally further contain pendant ethylenically unsaturated groups.
[0024] In some embodiments, the cyclic imide monomer comprises at least one (e.g., free radically polymerizable) ethylenically unsaturated group in combination with the α,β-unsaturation. In this embodiment, Y is an (e.g., free radically polymerizable) ethylenically unsaturated group, or R of the cyclic bis-imide further comprises a pendant (e.g., free radically polymerizable) ethylenically unsaturated group. In this embodiment, the number of ethylenically unsaturated polymerizable groups in the cyclic imide monomer is ≧2. In some embodiments, the number of ethylenically unsaturated polymerizable groups in the cyclic imide monomer is 3 or less.
[0025] The one or more additional ethylenically unsaturated groups can include, but are not limited to, the following structures: (meth)acrylic (i.e., (meth)acryloyl and (meth)acrylamide), vinyl, styrene, and ethynyl.
[0026] [ka] In the formula, each R 4 is independently H or C1-C4 alkyl.
[0027] Some representative cyclic imide monomers are as follows:
[0028] [Table 1-1]
[0029] [Table 1-2]
[0030] Although the illustrated cyclic imide monomers contain (meth)acrylate or carboxylic acid groups as representative (e.g., free radically polymerizable) ethylenically unsaturated groups, such monomers can alternatively have (meth)acrylamide, vinyl, styrenic, or ethynyl (e.g., free radically polymerizable) ethylenically unsaturated groups.
[0031] The molecular weight of the cyclic imide monomer is at least 150 g / mole. In exemplary embodiments, the molecular weight of the monomer is no greater than 1500, 1000, 750, or 500 g / mole.
[0032] Without intending to be bound by theory, it is believed that the addition-fragmentation monomers follow an addition-fragmentation pathway as shown in representative Reaction Scheme 1 below, where -R attached to the nitrogen atom is LY as previously described.
[0033] Reaction Scheme 1
[0034] [ka]
[0035] In Scheme 1, in step 1, a free radically polymerizable ethylenically unsaturated monomer, oligomer, or polymer represented by P· is added to the α,β-unsaturation of a cyclic imide monomer. In step 2, the cyclic monomer ring opens to give the following linear imide radical containing α,β-unsaturation:
[0036] [ka] changes to.
[0037] In step 3, the α-carbonyl tertiary radical (adjacent to the pendant dimethyl group) can initiate polymerization of the monomer.
[0038] In step 4, a free radically polymerizable ethylenically unsaturated oligomer, or polymer, represented by P·, is added to the α,β-unsaturation of the cyclic imide monomer. When at least two of the P groups are in a polymer chain, this reaction may be characterized as crosslinking.
[0039] The crosslink can be cleaved as shown in step 5 to form a stable α-carbonyl tertiary radical (represented by P·M) and a residue with α,β-unsaturation. The α,β-unsaturation can undergo radical addition as shown in step 4 and then be cleaved as shown in step 5. Thus, steps 4 and 5 can be repeated to further relieve the polymerization stress.
[0040] As shown in Reaction Scheme 1, addition-cleavage cyclic imides, which contain α,β-unsaturated monomers but lack additional ethylenically unsaturated polymerizable groups, provide several mechanisms for stress relief. Additionally, stress relief may also be the result of slower cure rates in the presence of cyclic imide addition-cleavage monomers, delaying the gel point. Post-gel shrinkage is a major factor in stress generation, and therefore delaying the gel point even slightly may lead to stress relief by allowing additional time for the material to flow during the curing process.
[0041] In another embodiment, the imide ring structure contains α,β-unsaturation and at least one additional (e.g., free radically polymerizable) ethylenically unsaturated group. As shown in Reaction Scheme 2 below, such cyclic imide monomers can provide the exact same polymer and monomer additions, as well as ring opening and chain scission cleavage, as shown in Reaction Scheme 1. In this embodiment, the additional ethylenically unsaturated group can also be polymerized, or in other words, crosslinked.
[0042] Reaction Scheme 2
[0043] [ka]
[0044] Although Reaction Scheme 2 is shown with a cyclic imide monomer having a particular -LY group attached to the nitrogen atom, the cyclic imide monomer may contain other -LY groups as described herein.
[0045] In another embodiment, the cyclic imide monomer comprises at least two imide ring structures comprising α,β-unsaturation. As shown in Reaction Scheme 3 below, such cyclic imide monomers can provide the exact same polymer and monomer additions, as well as ring opening and chain scission cleavage, as shown in Reaction Scheme 1. In Reaction Scheme 3 below, both imide ring structures are shown as simultaneously opening followed by simultaneous monomer addition. However, such addition and cleavage reactions can also occur sequentially, or in other words, each ring can react independently. Additionally, the R group may comprise an additional pendant (e.g., free radically polymerizable) ethylenically unsaturated group -LY, as described below. In this embodiment, the cyclic imide can also be polymerized, or in other words, crosslinked, as shown in Reaction Scheme 2.
[0046] Reaction Scheme 3
[0047] [ka]
[0048] Although Reaction Schemes 1-3 are shown using specific six-membered cyclic imide monomers, other cyclic imide monomers containing at least six covalently bonded atoms and α,β-unsaturation will follow the same or similar addition-fragmentation pathways.
[0049] In one embodiment, a method for preparing an α,β-unsaturated carbonyl-containing cyclic imide monomer is described, comprising reacting a dicarboxylic acid containing an α,β-unsaturated carbonyl with a dehydrating agent to form a cyclic compound containing an anhydride group and an α,β-unsaturated carbonyl, and reacting the anhydride group with a compound containing an amine group and a non-reactive group such as an alkyl or aryl, or a reactive group such as a carboxylic acid or a hydroxyl group to form a cyclic compound containing an α,β-unsaturated carbonyl and an imide group.
[0050] One representative dicarboxylic acid is 2,2-dimethyl-4-methylidenepentanedioic acid, as previously described. As previously described, other dicarboxylic acids can be utilized, provided that the dicarboxylic acid contains at least three consecutive carbon atoms with an α,β-unsaturated carbonyl between the acid groups.
[0051] Suitable dehydrating agents include acid anhydrides such as acetic anhydride and trifluoroacetic anhydride, phosphorus-based dehydrating agents such as phosphorus pentachloride or phosphorus pentoxide, and carbodiimide-based dehydrating agents such as dicyclohexylcarbodiimide.
[0052] Representative compounds containing an (eg, primary) amine group and an alkyl or aryl end group include 4-aminostyrene, butylamine, pentylamine, hexylamine, phenethylamine, and benzylamine.
[0053] A representative reaction scheme is as follows:
[0054] Reaction Scheme 4
[0055] [ka]
[0056] Suitable (e.g., aliphatic) compounds containing an amine group and a carboxylic acid group typically contain a primary amine group attached to a terminal acid group by an alkylene linking group that typically contains from 2 to 12 carbon atoms. Representative examples include, for example, 3-aminopropanoic acid, 4-aminobutanoic acid, 3-aminobutanoic acid, 2-aminobutanoic acid, 5-aminopentanoic acid, 2-aminopentanoic acid, 3-aminopentanoic acid, 4-aminopentanoic acid, 6-aminohexanoic acid, 2-aminohexanoic acid, 3-aminohexanoic acid, 4-aminohexanoic acid, 5-aminohexanoic acid, 7-aminoheptanoic acid, 6-aminoheptanoic acid, 5-aminoheptanoic acid, 4-aminoheptanoic acid, 3-aminoheptanoic acid, 2-aminoheptanoic acid, 8-aminooctanoic acid, 7-aminooctanoic acid, 6-aminooctanoic acid, 5-aminooctanoic acid, 4-aminooctanoic acid, 3-aminooctanoic acid, 2-aminooctanoic acid, 6-aminocaproic acid, and 12-aminododecanoic acid. Other suitable compounds that contain an amine group and a carboxylic acid group include (e.g., naturally occurring) amino acids such as glycine, alanine, valine, isoleucine, leucine, methionine, cysteine, phenylalanine, serine (also having an alcohol), threonine (as well as an alcohol), tyrosine, tryptophan, asparagine, glutamine, glutamic acid, and aspartic acid, histidine, arginine, or lysine.
[0057] A representative reaction scheme is as follows:
[0058] Reaction Scheme 5
[0059] [ka]
[0060] In some embodiments, the method of preparing a cyclic imide monomer further comprises reacting the carboxylic acid group of the nitrogen atom with a compound comprising an acid reactive group and an ethylenically unsaturated (e.g., free radically polymerizable) group.
[0061] The acid reactive group is typically an epoxy or aziridinyl group.
[0062] Representative epoxy compounds include glycidyl (meth)acrylate, thioglycidyl (meth)acrylate, 3-(2,3-epoxypropoxy)phenyl (meth)acrylate, 2-[4-(2,3-epoxypropoxy)phenyl]-2-(4-(meth)acryloyloxy-phenyl)propane, 4-(2,3-epoxypropoxy)cyclohexyl (meth)acrylate, 2,3-epoxycyclohexyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, and 4-hydroxybutyl acrylate glycidyl ether.
[0063] Representative aziridinyl compounds include N-(meth)acryloylaziridine, 2-(1-aziridinyl)ethyl (meth)acrylate, 4-(1-aziridinyl)butyl acrylate, 2-[2-(1-aziridinyl)ethoxy]ethyl (meth)acrylate, 2-[2-(1-aziridinyl)ethoxycarbonylamino]ethyl (meth)acrylate, 12-[2-(2,2,3,3-tetramethyl-1-aziridinyl)ethoxycarbonylamino]dodecyl (meth)acrylate, and 1-(2-propenyl)aziridine.
[0064] A representative reaction scheme is as follows:
[0065] Reaction Scheme 6
[0066] [ka]
[0067] The reaction of carboxylic acids with aziridinyl compounds is described in WO 2012 / 112304.
[0068] Suitable compounds containing an amine group and one or more hydroxyl groups include diols. Representative compounds include, for example, 3-amino-1-propanol, 5-amino-1-pentanol, and 3-amino-1,2-propanediol.
[0069] The cyclic imide compound having a hydroxyl group can be reacted with a compound containing an isocyanate group and a (meth)acrylate group.Representative isocyanate compounds include 2-isocyanatoethyl (meth)acrylate, 3-isocyanatopropyl (meth)acrylate, 4-isocyanatocyclohexyl (meth)acrylate, 4-isocyanatostyrene, 2-methyl-2-propenoyl isocyanate, 4-(2-(meth)acryloyloxyethoxycarbonylamino)phenyl isocyanate, allyl 2-isocyanatoethyl ether, and 3-isocyanato-1-propene, 3-isocyanato-1-propyne, 3-isopropenyl-α,α-dimethylbenzyl isocyanate.
[0070] The above reaction scheme illustrates the preparation of a monomer that contains an imide group and a single heterocycle that contains an α,β-unsaturated carbonyl.
[0071] In other embodiments, the cyclic imide monomer comprises at least two cyclic imide groups. One suitable method for preparing a cyclic bis-imide monomer comprises reacting a dicarboxylic acid containing an α,β-unsaturated carbonyl with a dehydrating agent to form a cyclic compound containing an anhydride group and an α,β-unsaturated carbonyl (as previously described in Reaction Scheme 4) and reacting the anhydride group with a diamine. A representative reaction scheme is as follows:
[0072] Reaction Scheme 7
[0073] [ka]
[0074] In some embodiments, the diamine is an aliphatic diamine in which the amine group is attached to an alkylene linking group. In some embodiments, the alkylene linking group contains 2 to 12 carbon atoms. The alkylene linking group may contain linear, branched, or cyclic moieties, as well as combinations thereof. Suitable examples include ethylenediamine, 1,3-propanediamine, 1,2-propanediamine, 1,4-butanediamine, 1,2-butanediamine, 1,3-butanediamine, 1,5-pentanediamine, 1,2-pentanediamine, 1,3-pentanediamine, 1,4-pentanediamine, 2,4-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine. , 1,12-dodecanediamine, isophoronediamine (cis and trans 5-amino-1,3,3-trimethylcyclohexanemethylamine), 1,5-diamino-2-methylpentane, trans-1,2-diaminocyclohexane, cis-1,2-diaminocyclohexane, 1,2-diphenyl-1,2-ethylenediamine, 4,4'-methylenebis(cyclohexylamine), and 4,4'-methylenebis(2-methylcyclohexylamine).
[0075] In another embodiment, the diamine is an aromatic diamine in which the amine groups are linked to a linking group that includes an arylene moiety. The linking group typically includes a C6-C12 arylene group. Suitable examples include p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, 4,4'-diaminobiphenyl, and 4,4'-methylenedianiline.
[0076] In another embodiment, the diamine may further comprise one or more pendant reactive (e.g., hydroxyl or carboxylic acid) groups. The pendant reactive (e.g., hydroxyl) groups can be reacted with a compound that comprises a co-reactive group and an ethylenically unsaturated (e.g., free radically polymerizable) group, such as an isocyanatoalkyl (meth)acrylate or an acid-reactive (meth)acrylate, as described above. A representative reaction scheme is as follows:
[0077] Reaction Scheme 8
[0078] [ka]
[0079] Reaction Scheme 9
[0080] [ka]
[0081] Although Reaction Schemes 4-6 are shown with a particular six-membered cyclic imide monomer, other cyclic imide monomers containing at least six covalently bonded atoms and α,β-unsaturation can be prepared using other dicarboxylic acids that contain an α,β-unsaturated carbonyl.
[0082] In some embodiments, a polymerizable composition is described that includes at least one addition-fragmentation cyclic imide monomer as described herein. The addition-fragmentation monomer of the polymerizable composition includes at least one cyclic imide monomer as described herein. The polymerizable composition may have a single cyclic imide monomer, a combination of two or more cyclic imide monomers, or at least one cyclic imide monomer in combination with a different addition-fragmentation monomer as described in WO 2012 / 112304.
[0083] The polymerizable composition typically comprises addition-fragmentation monomer(s) in an amount of at least 0.005, 0.006, 0.007, 0.008, 0.009, or 0.01% by weight, based on the total weight of the polymerizable monomer(s), oligomer(s), and polymer(s). In some embodiments, the amount of addition-fragmentation monomer(s) is at least 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 1.0% by weight, based on the total weight of the polymerizable monomer(s), oligomer(s), and polymer(s). The amount of addition-fragmentation monomer(s) is typically 10% by weight or less, based on the total weight of the polymerizable monomer(s), oligomer(s), and polymer(s). In some embodiments, the amount of addition-fragmentation monomer(s) is typically 9, 8, 7, 6, 5, 4, 3, 2, 1, or 0.5 wt.% or less, based on the total weight of the polymerizable monomer(s), oligomer(s), and polymer(s). Typically, the polymerizable composition contains a minimum amount of addition-fragmentation monomer(s) that reduces or eliminates polymerization-based stress. Excess addition-fragmentation cyclic imide monomer(s) can reduce the mechanical properties of the polymerized composition.
[0084] In some embodiments, the hardenable components of the present disclosure may optionally include one or more additional addition-cleavage agents. The addition-cleavage agents may include at least one ethylenically unsaturated end group and a backbone unit that includes an α,β-unsaturated carbonyl. The addition-cleavage agents may be cleavable by free radicals.
[0085] In some embodiments, the addition-cleavage agent can have the following structural formula:
[0086] [ka] During the ceremony, R 1 , R 2 , and R 3 are each independently m-Q-, a (hetero)alkyl group, or a (hetero)aryl group, provided that R 1 , R 2 , and R 3 At least one of them is Z m -Q-, Q is a linking group having a valence of m+1; Z is an ethylenically unsaturated polymerizable group; m is 1 to 6, preferably 1 to 2; each X 1 are independently -O- or -NR 4 -, wherein R 4 is H or C1-C4 alkyl, n is 0 or 1.
[0087] Addition-cleavage agents according to formula I are described in US Pat. No. 9,403,966, which is incorporated herein by reference in its entirety.
[0088] In embodiments where the addition-cleavage agent is multifunctional and contains at least two ethylenically unsaturated groups (e.g., Z is > 2 in Formula I), the material can function as a crosslinker and the crosslinks are unstable.
[0089] The ethylenically unsaturated portion Z of the monomer may include the following structures, including, but not limited to, (meth)acryloyl, vinyl, styrene, and ethynyl, which are more fully described with respect to the preparation of the compounds below.
[0090] [ka] In the formula, each R 4 is independently H or C1-C4 alkyl.
[0091] In some embodiments, Q is -O-, -S-, -NR 4 -, -SO2-, -PO2-, -CO-, -OCO-, -R 6 -, -NR 4 -CO-NR 4 -, NR4 -CO-O-, NR 4 -CO-NR 4 -, -CO-OR 6 -, -CO-NR 4 -R 6 -, -R 6 -CO-OR 6 -, -OR 6 -, -SR 6 --, -NR 4 -R 6 -,-SO2-R 6 -, -PO2-R 6 -, -CO-R 6 -, -OCO-R 6 -, -NR 4 -CO-R 6 -, NR 4 -R 6 -CO-O-, and NR 4 -CO-NR 4 -, wherein each R 4 is hydrogen, a C1-C4 alkyl group, or an aryl group, and each R 6 is an alkylene group having 1 to 6 carbon atoms, a 5- or 6-membered cycloalkylene group having 5 to 10 carbon atoms, or a divalent arylene group having 6 to 16 carbon atoms, with the proviso that Q to Z do not contain a peroxide bond.
[0092] In some embodiments, Q is of the formula -C r H 2r In some embodiments, Q is an alkylene such as -CH2-CH(OH)-CH2-, where r is 1 to 10. In other embodiments, Q is a hydroxyl-substituted alkylene such as -CH2-CH(OH)-CH2-. In some embodiments, Q is an aryloxy-substituted alkylene. In some embodiments, R 5 is an alkoxy substituted alkylene.
[0093] R 1 -X 1 -group (and optionally R 2 -X 2-yl) is typically selected from H2C=C(CH3C(O)-O-CH2-CH(OH)-CH2-O-, H2C=C(CH3C(O)-O-CH2-CH(O-(O)C(CH3)=CH2)-CH2-O-, H2C=C(CH3C(O)-O-CH(CH2OPh)-CH2-O-, H2C=C(CH3C(O)-O-CH2CH2-N(H)-C(O)-O-CH(CH2OPh)-CH2-O-, H2C=C(CH3C(O)-O-CH2-CH(O-(O)C-N(H)-CH2CH2-O-(O)C(CH3C=CH2)-CH2-O-, H2C=C(H)C(O)-O-(CH2)4-O-CH2-CH(OH)-CH2-O-, H2C=C(CH3C(O)-O-CH2-CH(O-(O)C-N(H)-CH2CH2-O-(O)C(CH3C=CH2)-CH2-O-, CH3-(CH2)7-CH(O-(O)C-N(H)-CH2CH2-O-(O)C(CH3C=CH2)-CH2-O-, H2C=C(H)C(O)-O-(CH2)4-O-CH2-CH(-O-(O)C(H)=CH2)-CH2-O-, and H2C=C(H)C(O)-O-CH2-CH(OH)-CH2-O-, H2C=C(H)C(O)-O-(CH2)4-O-CH2-CH(-O-(O)C(H)=CH2)-CH2-O-, and CH3-(CH2)7-CH(O-(O)C-N(H)-CH2CH2-O-(O)C(CH3C=CH2)-CH2-O-.
[0094] The compounds of formula I can be prepared from (meth)acrylate dimers and trimers by substitution, replacement, or condensation reactions. The starting (meth)acrylate dimers and trimers can be prepared by free radical addition of (meth)acryloyl monomers in the presence of a free radical initiator and a cobalt (II) complex catalyst using the method of U.S. Pat. No. 4,547,323, which is incorporated herein by reference. Alternatively, the (meth)acryloyl dimers and trimers can be prepared using cobalt chelate complexes using the process of U.S. Pat. No. 4,886,861 (Janowicz) or U.S. Pat. No. 5,324,879 (Hawthorne), which is incorporated herein by reference. In either process, the reaction mixture can contain a complex mixture of dimers, trimers, higher oligomers, and polymers, and the desired dimer or trimer can be separated from the mixture by distillation. Such syntheses are further described in US Pat. No. 9,403,966.
[0095] In some embodiments, the hardenable components of the present disclosure may further comprise at least one ethylenically unsaturated monomer or oligomer in combination with the addition-cleavage agent discussed above. In some embodiments, the ethylenically unsaturated monomer may be monofunctional, having a single (e.g., terminal) ethylenically unsaturated group. In other embodiments, such as dental restorations, the ethylenically unsaturated monomer may be polyfunctional. The phrase "polyfunctional ethylenically unsaturated" means that the monomers each contain at least two ethylenically unsaturated (e.g., free radical) polymerizable groups, such as (meth)acrylate groups.
[0096] In some embodiments, such ethylenically unsaturated groups are (meth)acryl-containing (e.g., terminal) free radically polymerizable groups such as (meth)acrylamides (HC=CHCON- and HC=CH(CH)CON-) and (meth)acrylates (CHCHCOO- and CHC(CH)COO-). Other ethylenically unsaturated polymerizable groups include vinyl (HC=C-), including vinyl ethers (HC=CHOCH-). The ethylenically unsaturated terminal polymerizable group(s) may be (meth)acrylate groups, especially for compositions that harden upon exposure to actinic (e.g., UV) radiation. Additionally, there may be more methacrylate functionality than acrylate functionality in hardenable dental compositions.
[0097] The ethylenically unsaturated monomer may include a variety of ethylenically unsaturated monomers known in the art for use in dental compositions.
[0098] In some embodiments, the hardenable (e.g., dental) component may include one or more ethylenically unsaturated (e.g., (meth)acrylate) low volume shrinkage monomers. In some embodiments, hardenable compositions useful as (e.g., filled) dental compositions (useful for fillings and restorations such as crowns) may include one or more low volume shrinkage monomers such that the compositions exhibit a watt shrinkage of less than about 4% or less than about 2%. In some embodiments, the watt shrinkage is 1.90% or less, or 1.80% or less, or 1.70% or less, or 1.60% or less. In some embodiments, the watt shrinkage is 1.50% or less, or 1.40% or less, or 1.30% or less, and in some embodiments, 1.25% or less, or 1.20% or less, or 1.15% or less, or 1.10% or less.
[0099] The ethylenically unsaturated monomers of the hardenable components are typically stable liquids at about 25° C., meaning that the monomers do not substantially polymerize, crystallize, or otherwise solidify when stored at room temperature (about 25° C.) for a typical shelf life of at least 30, 60, or 90 days. The viscosity of the monomers typically does not change (e.g., increase) by more than 10% of the initial viscosity.
[0100] In some embodiments, hardenable compositions useful as (e.g., filled) dental compositions (useful for fillings and restorations such as crowns) may include ethylenically unsaturated monomers that generally have a refractive index of at least 1.50. In some embodiments, the refractive index is at least 1.51, 1.52, 1.53, or higher. The inclusion of sulfur atoms and / or the presence of one or more aromatic moieties can raise the refractive index (compared to monomers of the same molecular weight lacking such substituents).
[0101] In some embodiments, the (unfilled) curable component may contain only one or more low shrinkage monomers in combination with the addition-cleavage agent(s). In other embodiments, the (unfilled) curable component may contain small concentrations of other monomer(s). By "other" we mean ethylenically unsaturated monomers, such as (meth)acrylate monomers, that are not low volume shrinkage monomers. The concentration of such other monomer(s) is typically not more than 20%, 19%, 18%, 17%, 16%, or 15% by weight of the (unfilled) curable component. The concentration of such other monomer(s) is typically not more than 5%, 4%, 3%, or 2% by weight of the filled curable component.
[0102] In some embodiments, low volume shrinkage monomers may include isocyanurate monomers as described in U.S. Pat. No. 9,237,990, tricyclodecane monomers as described in European Patent Application No. 10168240.9 filed July 2, 2010, polymerizable compounds having at least one cyclic aryl sulfide moiety as described in U.S. Patent Application Publication No. 2008 / 0194722, methylenedithiepane silanes as described in U.S. Pat. No. 6,794,520, oxetane silanes as described in U.S. Pat. No. 6,284,898, and di-, tri-, and / or tetra-(meth)acryloyl-containing materials as described in WO 2008 / 082881, each of which is incorporated herein by reference in its entirety.
[0103] In some embodiments, a majority of the (e.g., unfilled) hardenable components comprise one or more low volume shrinkage monomers. For example, at least 50%, 60%, 70%, 80%, 90% or more of the (e.g., unfilled) hardenable components may comprise low volume shrinkage monomer(s).
[0104] In some embodiments, the curable component may include at least one isocyanurate monomer. The isocyanurate monomer may include a trivalent isocyanuric acid ring as an isocyanurate core structure and at least two ethylenically unsaturated (e.g., free radical) polymerizable groups attached to at least two of the nitrogen atoms of the isocyanurate core structure via a (e.g., divalent) linking group. The linking group is the entire chain of atoms between the nitrogen atom of the isocyanurate core structure and the terminal ethylenically unsaturated group. The ethylenically unsaturated (e.g., free radical) polymerizable group is generally attached to the core or backbone unit via a (e.g., divalent) linking group.
[0105] The trivalent isocyanurate core structure may have the formula:
[0106] [ka] The divalent linking group may contain at least one nitrogen, oxygen, or sulfur atom. Such nitrogen, oxygen, or sulfur atom forms a urethane, ester, thioester, ether, or thioether bond. Ether bonds and especially ester bonds may be more beneficial than isocyanurate monomers containing urethane bonds to provide improved properties such as reduced shrinkage and / or improved mechanical properties, e.g., reduced viscosity while maintaining diametral tensile strength (DTS). Thus, in some embodiments, the divalent linking group of the isocyanurate monomer does not contain a urethane bond. In some embodiments, the divalent linking group contains an ester bond, such as an aliphatic diester bond or an aromatic diester bond.
[0107] The isocyanurate monomer may have the following general structure:
[0108] [ka] wherein R1 is a linear, branched, or cyclic alkylene, arylene, or alkarylene, optionally containing a heteroatom (e.g., oxygen, nitrogen, or sulfur); R2 is hydrogen or methyl; Z is an alkylene, arylene, or alkarylene linking group comprising at least one moiety selected from a urethane, an ester, a thioester, an ether, or a thioether, and combinations of such moieties; and at least one of R3 or R4 is
[0109] [ka] It is.
[0110] R1 is typically a straight-chain, branched-chain, or cyclic alkylene, optionally including heteroatoms, having 12 or fewer carbon atoms. In some preferred embodiments, R1 has 8, 6, or 4 or fewer carbon atoms. In some preferred embodiments, R1 includes at least one hydroxyl moiety.
[0111] In some embodiments, Z comprises an aliphatic or aromatic ester linkage, such as a diester linkage.
[0112] In some embodiments, Z further comprises one or more ether moieties. Thus, the linking group may comprise a combination of an ester moiety or a diester moiety and one or more ether moieties.
[0113] In embodiments in which the isocyanurate monomer is a di(meth)acrylate monomer, R3 or R4 is hydrogen, alkyl, aryl, or alkaryl, optionally including a heteroatom.
[0114] R1 is generally derived from a starting (e.g., hydroxy-terminated) isocyanurate precursor. A variety of isocyanurate precursor materials are commercially available from TCI America, Inc., Portland, Oreg. The structures of exemplary isocyanurate precursor materials are shown below.
[0115] [ka]
[0116] The isocyanurate (meth)acrylate monomers disclosed herein having a linking group that includes an oxygen atom of an ester moiety can be prepared by reaction of a hydroxy or epoxy terminated isocyanurate with a (meth)acrylated carboxylic acid such as mono-(2-methacryloxyethyl)phthalic acid and mono-(2-methacryloxyethyl)succinic acid.
[0117] Suitable (meth)acrylated carboxylic acids include, for example, mono-(2-methacryloxyethyl)phthalic acid(s), mono-(2-methacryloxyethyl)succinic acid, and mono-(2-methacryloxyethyl)maleic acid. Alternatively, the carboxylic acid may contain a (meth)acrylamide functional group, such as methacrylamide derivatives of naturally occurring amino acids, such as methacrylamide glycine, methacrylamide leucine, and methacrylamide alanine.
[0118] In some embodiments, a single (meth)acrylated carboxylic acid is reacted with a single hydroxyl-terminated isocyanurate (e.g., tris-(2-hydroxyethyl)isocyanurate). When a sufficient molar ratio of (meth)acrylated carboxylic acid is utilized such that all hydroxyl groups of the ring are reacted, such synthesis can produce a single reaction product in which each of the free radical end groups attached to the nitrogen atom of the trivalent isocyanuric acid ring is the same. However, when a single epoxy-terminated isocyanurate is reacted with a single carboxylic acid, the reaction product generally contains multiple isomers in the reaction product.
[0119] When two different hydroxy or epoxy terminated isocyanurates and / or two different (e.g., (meth)acrylated) carboxylic acids are utilized, a statistical mixture of reaction products is obtained based on the relative amounts of the reactants. For example, when a mixture of (meth)acrylated aromatic carboxylic acids and (meth)acrylated aliphatic carboxylic acids is utilized, some of the free radical terminated divalent linking groups attached to the nitrogen atoms of the trivalent isocyanuric acid ring will contain aromatic groups, while others will not. Furthermore, when a combination of (e.g., one equivalent) of a hydroxyl terminated carboxylic acid and (e.g., two equivalents) of a monocarboxylic acid (such as octanoic acid) is reacted with a single hydroxyl terminated isocyanurate (e.g., tris-(2-hydroxylethyl)isocyanurate), a mono(meth)acrylated isocyanurate can be prepared as further described in U.S. Pat. No. 9,237,990. Such mono(meth)acrylated isocyanurates are suitable for use as reactive diluents.
[0120] Alternatively, isocyanurate (meth)acrylate monomers with ether group-containing linking groups can be synthesized. For example, in one exemplary synthesis, phthalic anhydride can be reacted with mono-methacrylated di-, tri-, tetra-, or polyethylene glycol in the presence of catalytic amounts of 4-(dimethylamino)pyridine (DMAP) and butylated hydroxytoluene inhibitor (BHT) at 95° C. for 3-6 hours to form mono-methacrylated polyethylene glycol phthalate monoester. The resulting methacrylated acid can be reacted with tris-(2-hydroxyethyl)isocyanurate in acetone at 0-5° C. using dicyclohexyl carbodiimide (DCC) and then at room temperature. Such a reaction scheme is shown below.
[0121] [ka]
[0122] In another exemplary synthesis, tris(2-hydroxyethyl)isocyanurate can be reacted with ethylene oxide to form a hydroxyl-terminated polyethylene glycol. The OH terminus can be esterified with meth(acrylic) acid to give a product in which the linking group is a polyether. Such a reaction scheme is shown below.
[0123] [ka]
[0124] In some embodiments, the isocyanurate monomer may be a multi(meth)acrylate, such as a di(meth)acrylate isocyanurate monomer or a tri(meth)acrylate isocyanurate monomer.
[0125] The di(meth)acrylate monomer can have the following structure:
[0126] [ka] wherein R1, R2, R3, and Z are as described above; R6 is a linear, branched, or cyclic alkylene, arylene, or alkarylene, optionally containing a heteroatom (e.g., oxygen, nitrogen, or sulfur); and Y is an alkylene, arylene, or alkarylene linking group comprising at least one moiety selected from a urethane, an ester, a thioester, an ether, or a thioether, and combinations of such moieties.
[0127] Exemplary di(meth)acrylate isocyanurate monomers include the following:
[0128] [ka]
[0129] In some embodiments, the tri(meth)acrylate monomer can have the following structure:
[0130] [ka] During the ceremony, R1, R5, and R6 are independently a straight, branched, or cyclic alkylene, arylene, or alkarylene group, optionally containing a heteroatom (e.g., oxygen, nitrogen, or sulfur); R2 is hydrogen or methyl; X, Y, and Z are independently an alkylene, arylene, or alkarylene linking group containing at least one moiety selected from a urethane, an ester, a thioester, an ether, a thioether, or a combination of such moieties; and R2 is hydrogen or methyl.
[0131] In some embodiments, R1, R5, and R6 comprise at least one hydroxyl moiety.
[0132] Exemplary tri(meth)acrylate isocyanurate monomers include, for example, the following:
[0133] [ka]
[0134] In some embodiments, the curable component may include at least one tricyclodecane monomer. The tricyclodecane monomer may include a single monomer or a blend of two or more tricyclodecane monomers. The concentration of the multifunctional ethylenically unsaturated tricyclodecane monomer in the unfilled or filled curable component may be the same as that described for the multifunctional ethylenically unsaturated isocyanurate monomer.
[0135] In some embodiments, the curable component may include a multifunctional ethylenically unsaturated isocyanurate monomer and a multifunctional ethylenically unsaturated tricyclodecane monomer in a weight ratio ranging from about 1.5:1 to 1:1.5.
[0136] The tricyclodecane monomer may have the following core structure (ie, backbone unit (U)):
[0137] [ka]
[0138] In some embodiments, the tricyclodecane monomer can have the following core structure (ie, backbone unit (U)):
[0139] [ka]
[0140] Such tricyclodecane monomers can be prepared, for example, from the following starting materials:
[0141] [ka] (a+b)=1 and (c+d)=1, Mw=312.5
[0142] [ka] (a+b)=1 and (c+d)=1, Mw=418.6
[0143] [ka] (a+b)=1 and (c+d)=1, Mw=388.6
[0144] In some embodiments, the backbone unit (U) may include one or two spacer units (S) bonded to the backbone unit (U) through an ether bond. At least one spacer unit (S) includes a CH(Q)-OG chain, where each group G includes a (meth)acrylate moiety, and Q includes at least one group selected from hydrogen, alkyl, aryl, alkaryl, and combinations thereof. In some embodiments, Q is hydrogen, methyl, phenyl, phenoxymethyl, and combinations thereof. G may be bonded to the spacer unit (S) through a urethane moiety.
[0145] In some embodiments, the spacer unit(s) (S) typically comprises:
[0146] [ka] In the formula, m is 1 to 3, n is 1 to 3, and Q is hydrogen, methyl, phenyl, or phenoxymethyl.
[0147] In other embodiments, the spacer unit(s) (S) typically comprises:
[0148] [ka] Wherein M=phenyl.
[0149] In some embodiments, the tricyclodecane monomer has the structure:
[0150] [ka] wherein for each of these tricyclodecane monomer structures, a, b are 0-3, c, d=0-3, (a+b) is 1-6, (c+d) is 1-6, and Q is independently hydrogen, methyl, phenyl, or phenoxymethyl.
[0151] Some exemplary species of such multifunctional ethylenically unsaturated tricyclodecane monomers are set forth in the table below.
[0152] [Table 2-1]
[0153] [Table 2-2]
[0154] In some embodiments, the linking group of the isocyanurate and tricyclodecane monomers may be sufficiently low in molecular weight so that the monomers are stable liquids at 25° C. However, the linking group(s) may be higher in molecular weight than, for example, the oxygen atom of 2,2-bis[4-(2-hydroxy-3-methacryloyloxypropoxy)phenyl]propane ("BisGMA"), a common monomer utilized in dental compositions that links a (meth)acrylate group to an aromatic ring. The molecular weight of the linking group(s) of the described monomers is typically at least 50 g / mol or 100 g / mol. In some embodiments, the molecular weight of the linking group is at least 150 g / mol. The molecular weight of the linking group is typically about 500 g / mol or less. In some embodiments, the molecular weight of the linking group is 400 g / mol or 300 g / mol or less.
[0155] In some embodiments, the (i.e., calculated) molecular weight of the low shrinkage (e.g., isocyanurates and tricyclodecane) monomers is typically 2000 g / mole or less. In some embodiments, the molecular weight of the monomer is about 1500 g / mole or less, or 1200 g / mole or less, or 1000 g / mole or less. The molecular weight of the monomer is typically at least 600 g / mole.
[0156] Increasing molecular weight without forming solids at 25° C. can be achieved by a variety of synthetic approaches, as described above. In some embodiments, the linking group has one or more pendant substituents. For example, the linking group may contain one or more hydroxyl group substituents, such as in the case of a linking group that includes an alkoxy segment. In other embodiments, the linking group is branched and / or contains at least one (i.e., aliphatic) cyclic moiety and / or contains at least one aromatic moiety.
[0157] In some embodiments, by-products are formed during the synthesis of the monomer that may be solid at about 25° C. (i.e., + / - 2° C.). Such by-products are typically removed from the liquid monomer. Thus, the liquid monomer is substantially free of such solid fractions. However, it is contemplated that the liquid monomer may further include solid reaction by-products that are soluble (e.g., non-crystalline) in the liquid monomer.
[0158] In some embodiments, the hardenable component may include a polymerizable compound having at least one cyclic aryl sulfide moiety having at least one (meth)acryloyl moiety.
[0159] Such polymerizable compounds are referred to herein as hybrid monomers or hybrid compounds. The cyclic allyl sulfide moiety may contain at least one 7- or 8-membered ring with two heteroatoms in the ring, one of which is sulfur. Most typically, both heteroatoms are sulfur, which may optionally be present as part of a SO, SO2, or SS moiety. In other embodiments, the ring may contain a second different heteroatom in the ring, such as oxygen or nitrogen, in addition to the sulfur atom. In addition, the cyclic allyl moiety may contain multiple ring structures, i.e., have two or more cyclic allyl sulfide moieties. The (meth)acryloyl moiety is preferably a (meth)acryloyloxy (i.e., a (meth)acrylate moiety) or a (meth)acryloylamino (i.e., a (meth)acrylamide moiety).
[0160] In some embodiments, the low shrinkage monomer may include those represented by the following formula:
[0161] [ka]
[0162] In the above formula, each X may be independently selected from S, O, N, C (e.g., CH2 or CRR, where each R is independently H or an organic group), SO, SO2, N-alkyl, N-acyl, NH, N-aryl, carboxyl, or carbonyl groups, provided that at least one X is S or a group that includes S. Preferably, each X is S.
[0163] Y is either an alkylene (e.g., methylene, ethylene, etc.) optionally containing a heteroatom, carbonyl, or acyl, or is absent, thereby indicating the size of the ring, typically 7-10 members, although larger rings are also contemplated. Preferably, the ring is either a 7- or 8-membered ring, and thus Y is either absent or methylene, respectively. In some embodiments, Y is either absent or a C1-C3 alkylene, optionally containing a heteroatom, carbonyl, acyl, or combinations thereof.
[0164] Z is O, NH, N-alkyl (straight or branched chain), or N-aryl (phenyl or substituted phenyl).
[0165] The R' group represents a linker selected from alkylene (typically having 2 or more carbon atoms, i.e. excluding methylene), alkylene optionally containing heteroatoms (e.g., O, N, S, SS, SO, SO2), arylene, alicyclic, carbonyl, siloxane, amido (-CO-NH-), acyl (-CO-O-), urethane (-O-CO-NH-), and urea (-NH-CO-NH-) groups, and combinations thereof. In certain embodiments, R' comprises an alkylene group, typically methylene or a longer group, which may be either linear or branched, and which may be unsubstituted or substituted with aryl, cycloalkyl, halogen, nitrile, alkoxy, alkylamino, dialkylamino, akylthio, carbonyl, acyl, acyloxy, amido, urethane groups, urea groups, cyclic arylsulfide moieties, or combinations thereof.
[0166] R″ is selected from H and CH3, and “a” and “b” are independently 1 to 3.
[0167] Optionally, the cyclic arylsulfide moiety may be further substituted on the ring with one or more groups selected from linear or branched alkyl, aryl, cycloalkyl, halogen, nitrile, alkoxy, alkylamino, dialkylamino, akylthio, carbonyl, acyl, acyloxy, amide, urethane groups, and urea groups. In some embodiments, the selected substituents do not interfere with the hardening reaction.
[0168] Exemplary low shrinkage monomers may include an 8-membered cyclic aryl sulfide moiety having two sulfur atoms in the ring and a linker (i.e., ring-OC(O)-) attached directly to the 3-position of the ring bearing the acyl group. Typically, the weight average molecular weight (MW) of the hybrid monomer ranges from about 400 to about 900, and in some embodiments is at least 250, more typically at least 500, and most typically at least 800.
[0169] Representative polymerizable compounds having at least one cyclic allyl sulfide moiety having at least one (meth)acryloyl moiety include the following:
[0170] [ka]
[0171] The inclusion of a polymerizable compound having at least one cyclic aryl sulfide moiety can provide a synergistic combination of low volumetric shrinkage combined with high diametral tensile strength.
[0172] In some embodiments, the hardenable component has the following general formula:
[0173] [ka] (wherein each X independently represents an oxygen atom (O) or a nitrogen atom (N), Y and A each independently represent an organic group, R 1 represents -C(O)C(CH3)=CH2, and / or (ii) q=0, R 2 represents -C(O)C(CH3)=CH2, m is 1 to 5, n is 0 to 5, p and q are each independently 0 or 1, and R 1 and R 2 may include low shrinkage monomers including at least one di-, tri-, and / or tetra-(meth)acryloyl-containing material having p=0, where p=0, and Y=0. In some embodiments, when p=0, Y does not represent -NHCHCH-. This material is a derivative of bisphenol A, but when other low volume shrinkage monomers such as isocyanurate monomers and / or tricyclodecane monomers are used, the dental composition does not include (meth)acrylate monomers derived from bisphenol A.
[0174] In some embodiments, the multifunctional low shrinkage monomers (e.g., isocyanurates and tricyclodecane) may be (e.g., highly) viscous liquids at about 25° C., but are flowable. The viscosity, which can be measured with a Haake RotoVisco RV1 instrument, as described in European Patent Application Publication No. 10168240.9, filed July 2, 2010, is typically at least 300, or 400, or 500 Pa. * s and 10,000 Pa * In some embodiments, the viscosity is 5000 or 2500 Pa at room temperature. * s or less.
[0175] In some embodiments, the polymerizable dental compositions may include a wide variety of "other" ethylenically unsaturated monomers (with or without acid functionality), epoxy-functional (meth)acrylate resins, vinyl ethers, and the like.
[0176] In some embodiments, the polymerizable dental composition may further include one or more ethylenically unsaturated compounds having acidic functionality. For example, the inclusion of such compounds may be useful for polymerizable dental compositions intended to exhibit self-adhesive properties, i.e., polymerizable dental compositions that do not require a separate step of etching with acid to facilitate bonding of the dental composition to a dental structure. Surprisingly, it has been found that the cyclic imide monomers of the present disclosure are more efficient as stress reducers than known addition-cleavage agents, particularly with respect to self-adhesive compositions. More specifically, it has been found that the cyclic imide monomers of the present disclosure, in combination with acidic monomers, exhibit significantly greater stress reduction per weight used, stronger self-adhesion, and maintain adequate levels of other desirable properties, compared to known addition-cleavage agents.
[0177] In some embodiments, the acidic functional group may include an oxyacid (i.e., an oxygen-containing acid) of carbon, sulfur, phosphorus, or boron. As used herein, an ethylenically unsaturated compound having an acidic functional group is meant to include monomers, oligomers, and polymers having ethylenic unsaturation and acid and / or acid precursor functional groups. Acid precursor functional groups include, for example, anhydrides, acid halides, and pyrophosphates. The acidic functional group may include a carboxylic acid functional group, a phosphoric acid functional group, a phosphonic acid functional group, a sulfonic acid functional group, or a combination thereof.
[0178] In some embodiments, the ethylenically unsaturated compound having an acidic functional group may be, for example, an α,β-unsaturated acidic compound, such as glycerol phosphate mono(meth)acrylate, glycerol phosphate di(meth)acrylate, hydroxyethyl(meth)acrylate (e.g., HEMA) phosphate, bis((meth)acryloxyethyl)phosphate, ((meth)acryloxypropyl)phosphate, bis((meth)acryloxypropyl)phosphate, bis((meth)acryloxy)propyloxyphosphate, (meth)acryloxyhexylphosphate, bis((meth)acryloxyhexyl)phosphate, (meth)acryloxyoctylphosphate, Acid salts, bis((meth)acryloyloxyoctyl)phosphates, (meth)acryloyloxydecylphosphates, bis((meth)acryloyloxydecyl)phosphates, caprolactone methacrylate phosphates, citric acid di- or tri-methacrylates, poly(meth)acrylated oligomaleic acids, poly(meth)acrylated polymaleic acids, poly(meth)acrylated poly(meth)acrylic acids, poly(meth)acrylated polycarboxyl-polyphosphonic acids, poly(meth)acrylated polychlorophosphoric acids, poly(meth)acrylated polysulfonates, poly(meth)acrylated polyboric acids, etc., which may be used as components. Also, monomers, oligomers, and polymers of unsaturated carboxylic acids such as (meth)acrylic acid, aromatic (meth)acrylated acids (e.g., methacrylated trimellitic acid), and anhydrides thereof may be used.
[0179] In some embodiments, the polymerizable dental composition can include an ethylenically unsaturated compound having an acidic functional group with at least one P-OH moiety. Such compositions are self-adhesive and non-aqueous. For example, such compositions can include at least one (meth)acryloxy group and at least one -OP(O)(OH) x A first compound comprising a group, where x=1 or 2, and at least one -OP(O)(OH) x a first compound, wherein the at least one (meth)acryloxy group and at least one -OP(O)(OH) group are linked together by a C1-C4 hydrocarbon group; x wherein x=1 or 2 and at least one -OP(O)(OH) x The group and at least one (meth)acryloxy group are C5 to C 12 It can include a second compound, an ethylenically unsaturated compound without acid functionality, an initiator system, and a filler, linked together by a hydrocarbon group.
[0180] In some embodiments, the polymerizable dental composition can include a solvent (e.g., alcohols (e.g., propanol, ethanol), ketones (e.g., acetone, methyl ethyl ketone), esters (e.g., ethyl acetate), other non-aqueous solvents (e.g., dimethylformamide, dimethylacetamide, dimethylsulfoxide, 1-methyl-2-pyrrolidinone), and water).
[0181] In some embodiments, the polymerizable dental composition may contain additives such as indicators, dyes, pigments, inhibitors, accelerators, viscosity modifiers, humectants, buffers, radical and cationic stabilizers (e.g., BHT), and other similar ingredients that would be apparent to one skilled in the art. Drugs or other therapeutic substances may be added to the polymerizable dental composition. Examples include fluoride sources, whitening agents, anticaries agents (e.g., xylitol), calcium sources, phosphorus sources, remineralizing agents (e.g., calcium phosphate compounds), enzymes, breath fresheners, anesthetics, coagulants, acid neutralizers, chemotherapeutic agents, immune response modifiers, thixotropic agents, polyols, anti-inflammatory agents, antibacterial agents (in addition to antibacterial lipid components), antifungal agents, agents for treating xerostomia, desensitizing agents, and the like, which are types that are often used in dental compositions. Also, combinations of any of the above additives may be used. The selection and amount of any one such additive may be selected by one skilled in the art to achieve the desired results without undue experimentation.
[0182] In some embodiments, the concentrations of ingredients in the polymerizable / hardenable dental compositions described herein can be expressed relative to the (i.e., unfilled) hardenable component (or polymerizable resin portion) of the dental composition. In some embodiments where the composition further comprises a filler, the concentrations of ingredients can also be expressed relative to the total (i.e., filled) composition. When the composition does not comprise a filler, the hardenable component (or polymerizable resin portion) is the same as the total composition.
[0183] In some embodiments, the unfilled polymerizable dental composition can include from 0.1 wt % to 30 wt %, from 0.1 wt % to 10 wt %, from 0.1 wt % to 5 wt %, or from 0.5 wt % to 5 wt % of an addition-cleavage agent comprising any of the cyclic imide monomers described above, based on the total weight of the unfilled polymerizable dental composition.
[0184] In embodiments that include an addition-cleavage agent in addition to an addition-cleavage agent that includes a cyclic imide monomer, the unfilled polymerizable dental composition can include from 0.1 wt % to 30 wt %, from 0.1 wt % to 10 wt %, from 0.1 wt % to 5 wt %, or from 0.5 wt % to 5 wt % of a non-cyclic imide monomer that includes an addition-cleavage agent, based on the total weight of the unfilled polymerizable dental composition.
[0185] In some embodiments, the unfilled polymerizable dental composition can comprise from 10% to 95%, from 15% to 45%, or from 25% to 40% by weight of at least one ethylenically unsaturated monomer or oligomer (other than the addition-cleavage agent) based on the total weight of the unfilled polymerizable dental composition.
[0186] In some embodiments, the unfilled polymerizable dental composition may comprise from 10% to 95%, from 10% to 40%, or from 15% to 30% by weight of the ethylenically unsaturated isocyanurate monomer(s) based on the total weight of the unfilled polymerizable dental composition.
[0187] In some embodiments, the unfilled polymerizable dental composition may comprise at least 1 wt%, at least 3 wt%, or at least 5 wt% of an ethylenically unsaturated compound having an acidic functional group, based on the total weight of the unfilled composition. In some embodiments, the unfilled polymerizable dental composition may comprise up to 80 wt%, up to 70 wt%, or up to 60 wt% of an ethylenically unsaturated compound having an acidic functional group, based on the total weight of the unfilled composition.
[0188] Materials with high polymerization stress upon curing will generate distortions in tooth structure. One clinical consequence of such stresses can be a reduction in the life span of restorations. As described in RR Cara et al, Particulate Science and Technology 28;191-206 (2010), the stresses present in composite materials can be transferred through the adhesive interface to the tooth structure, causing cuspal deflection and cracking in the surrounding dentin and enamel, and causing post-operative hypersensitivity. In some embodiments, the (e.g., filled) dental compositions described herein (useful for restorations such as fillings and crowns) typically exhibit a stress deflection of 2.0, or 1.8, or 1.6, or 1.4, or 1.2, or 1.0, or 0.8, or 0.6 micrometers or less.
[0189] In some embodiments, the inclusion of an addition-cleavage agent(s) results in a significant reduction in stress even when the stress deflection is greater than 2.0 micrometers. For example, the inclusion of an addition-cleavage agent(s) may reduce the stress from about 7 micrometers to about 6 micrometers, or about 5 micrometers, or about 4 micrometers, or about 3 micrometers.
[0190] In some embodiments, the polymerizable dental composition may include, in addition to the hardenable component, one or more fillers. The fillers may be selected from one or more of a wide variety of materials suitable for incorporation into compositions used in dental applications, such as fillers currently used in dental restorative compositions.
[0191] In some embodiments, the filler can be an inorganic material. It can also be a cross-linked organic material that is insoluble in the polymerizable resin and is optionally filled with an inorganic filler. The filler is generally non-toxic and suitable for use in the mouth. The filler can be radiopaque, radiolucent, or non-radiopaque. Fillers used in dental applications are typically ceramic in nature.
[0192] Non-acid-reactive inorganic filler particles include quartz (ie, silica), submicron silica, zirconia, submicron zirconia, and non-vitreous microparticles of the type described in US Pat. No. 4,503,169 (Randklev).
[0193] The filler may also be an acid-reactive filler. Suitable acid-reactive fillers include metal oxides, glasses, and metal salts. Typical metal oxides include barium oxide, calcium oxide, magnesium oxide, and zinc oxide. Typical glasses include borate glasses, phosphate glasses, and fluoroaluminosilicate ("FAS") glasses. FAS glasses typically contain sufficient leachable cations so that a set dental composition is formed when the glass is mixed with the components of the settable composition. The glasses also typically contain sufficient leachable fluoride ions so that the set composition has cariostatic properties. The glasses can be made from a melt containing fluoride, alumina, and other glass-forming raw materials using techniques well known to those skilled in the art of FAS glass manufacturing. FAS glasses are typically in the form of particles that are sufficiently finely divided so that they can be conveniently mixed with other cement components and the resulting mixture performs well when used in the mouth.
[0194] Generally, the average particle size (typically diameter) of FAS glass is 12 micrometers or less, typically 10 micrometers or less, more typically 5 micrometers or less, as measured, for example, using a sedimentation particle size analyzer.Suitable FAS glasses are well known to those skilled in the art and are available from a wide variety of commercial sources, and many are found in currently available glass ionomer cements, such as those sold under the trade names VITREMER, VITREBOND, RELY X LUTING CEMENT, RELY X LUTING PLUS CEMENT, PHOTAC-FIL QUICK, KETAC-MOLAR and KETAC-FIL PLUS (3M ESPE Dental Products, St. Paul, Minnesota), FUJI II LC and FUJI IX (GC Dental Industrial, Tokyo, Japan), and CHEMFIL Superior (Dentsply International, York, Pennsylvania).If desired, mixtures of fillers can be used.
[0195] Other suitable fillers are disclosed in U.S. Patent Nos. 6,387,981 (Zhang et al.) and 6,572,693 (Wu et al.), as well as PCT Publication Nos. WO 01 / 30305 (Zhang et al.), WO 01 / 30307 (Zhang et al.), and WO 03 / 063804 (Wu et al.). Filler components described in these references include nano-sized silica particles, nano-sized metal oxide particles, and combinations thereof. Nanofillers are also described in U.S. Patent Nos. 7,090,721 (Craig et al.), 7,090,722 (Budd et al.), and 7,156,911, as well as U.S. Patent No. 7,649,029 (Kolb et al.).
[0196] Examples of suitable organic filler particles include filled or unfilled ground polycarbonates, polyepoxides, poly(meth)acrylates, etc. Commonly used dental filler particles are quartz, submicron silica, and non-vitreous microparticles of the type described in U.S. Pat. No. 4,503,169 (Randklev).
[0197] Mixtures of these fillers can also be used, as well as combination fillers made from organic and inorganic materials.
[0198] Fillers can be either particulate or fibrous in nature. Particulate fillers may generally be defined as having a length to width ratio or aspect ratio of 20:1 or less, more commonly 10:1 or less. Fibers can be defined as having an aspect ratio of greater than 20:1, or more commonly greater than 100:1. The shape of the particles can vary from spherical to ellipsoidal, or more planar such as flakes or discs. Macroscopic properties can be highly dependent on the shape of the filler particles, especially the uniformity of the shape.
[0199] Micrometer-sized particles are very effective in improving wear properties after curing. In contrast, nanoscale fillers are commonly used as viscosity and thixotropy modifiers. Due to their small size, high surface area, and associated hydrogen bonding, these materials are known to assemble into cohesive networks.
[0200] In some embodiments, the polymerizable dental composition may include nanoscale particulate fillers (i.e., fillers including nanoparticles) having an average primary particle size of less than about 0.100 micrometers (i.e., micrometers), or less than 0.075 micrometers. As used herein, the term "primary particle size" refers to the size of a non-associated single particle. The average primary particle size can be determined by cutting a thin sample of the set dental composition and measuring the particle diameter of about 50-100 particles using a transmission electron micrograph at 300,000 times magnification and calculating the average. The fillers can have a unimodal or multimodal (e.g., bimodal) particle size distribution. Nanoscale particulate materials typically have an average primary particle size of at least about 2 nanometers (nanometer, nm), or at least about 7 nm. In some embodiments, the nanoscale particulate materials have an average primary particle size of about 50 nm or less, or about 20 nm or less in size. The average surface area of such fillers is at least about 20 square meters per gram (m 2 / g), at least about 50m 2 / g, or at least about 100m 2 / g.
[0201] In some embodiments, the polymerizable dental composition includes silica nanoparticles. The silica particles can be made from an aqueous colloidal dispersion (i.e., sol or aquasol) of silica. Colloidal silica is typically at a concentration of about 1-50 weight percent in the silica sol. Colloidal silica sols that can be used are commercially available with different colloidal sizes, see Surface & Colloid Science, Vol. 6, ed. Matijevic, E., Wiley Interscience, 1973. Some silica sols used to make fillers are supplied as a dispersion of amorphous silica in an aqueous medium, have a low sodium concentration, and can be acidified by mixing with a suitable acid (e.g., Ludox colloidal silica from EI Dupont de Nemours & Co.).
[0202] In some embodiments, the silica particles in the sol have an average particle diameter of about 5-100 nm, 10-50 nm, or 12-40 nm.
[0203] In some embodiments, the dental composition comprises zirconia nanoparticles.
[0204] Suitable nano-sized zirconia nanoparticles can be prepared using hydrothermal techniques, as described in US Pat. No. 7,241,437 (Davidson et al.).
[0205] In some embodiments, nanoparticles of a lower refractive index (e.g., silica) are used in combination with nanoparticles of a higher refractive index (e.g., zirconia) to index match the filler to the refractive index of the polymerizable resin (within 0.02 refractive index).
[0206] In some embodiments, the nanoparticles are in the form of nanoclusters, i.e., groups of two or more particles associated by relatively weak intermolecular forces that cause the particles to aggregate even when dispersed in a settable resin. Nanoclusters can include substantially amorphous clusters of non-heavy (e.g., silica) particles, and amorphous heavy metal oxide (i.e., having an atomic number greater than 28) particles, such as zirconia. The particles of the nanoclusters may have an average diameter of less than about 100 nm. Suitable nanocluster fillers are described in U.S. Patent No. 6,730,156 (Windisch et al.), which is incorporated herein by reference in its entirety.
[0207] In some embodiments, the polymerizable dental composition may include nanoparticles and / or nanoclusters surface treated with an organometallic coupling agent to enhance the bond between the filler and the resin. The organometallic coupling agent may be functionalized with reactive curing groups such as acrylate, methacrylate, vinyl groups, etc.
[0208] Suitable copolymerizable organometallic compounds may have the general formula: CH2=C(CH3)m Si(OR) n or CH2=C(CH3) m C=OOASi(OR) n where m is 0 or 1, R is an alkyl group having 1 to 4 carbon atoms, A is a divalent organic linking group, and n is 1 to 3. Suitable coupling agents include γ-methacryloxypropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and the like.
[0209] In some embodiments, a combination of surface modifiers may be useful, with at least one of the surface modifiers having a functional group capable of copolymerizing with the settable resin. Other surface modifiers that do not generally react with the settable resin may be included to enhance dispersibility or rheological properties. Examples of this type of silane include, for example, aryl polyether, alkyl, hydroxyalkyl, hydroxyaryl, or aminoalkyl functional silanes.
[0210] The surface modification can be performed either before or after mixing with the monomer. The organosilane surface treatment compound is typically combined with the nanoparticles before incorporation into the resin. The required amount of surface modifier depends on several factors, such as particle size, particle type, modifier molecular weight, and modifier type. Generally, approximately a monolayer of modifier may be attached to the surface of the particle.
[0211] In embodiments having a filler, the polymerizable dental composition may include any of the above-mentioned fillers (including any combination thereof) in an amount of 1 wt% to 95 wt%, 5 wt% to 90 wt%, 30 wt% to 90 wt%, 50 wt% to 90 wt%, or 55 wt% to 85 wt%, based on the total weight of the filled polymerizable dental composition. In some embodiments useful as a dental restorative, the polymerizable dental composition may include any of the above-mentioned fillers (including any combination thereof) in an amount of 70 wt% to 90 wt%, or 72 wt% to 85 wt%, based on the total weight of the filled polymerizable dental composition. In some embodiments useful as a flowable adhesive, the polymerizable dental composition may include any of the above-mentioned fillers (including any combination thereof) in an amount of 55 wt% to 70 wt%, or 58 wt% to 65 wt%, based on the total weight of the filled polymerizable dental composition.
[0212] In some embodiments, the polymerizable dental composition can be used to treat oral surfaces such as teeth, as known in the art. In some embodiments, the composition can be hardened by curing after application of the dental composition. For example, when the hardenable dental composition is used as a restorative material such as a dental filling material, the method generally includes applying the polymerizable dental composition to an oral surface (e.g., a cavity) and hardening the composition. In some embodiments, a dental adhesive may be applied prior to application of the polymerizable dental restorative material described herein. The dental adhesive is also typically hardened by curing simultaneously with the hardening of the highly filled polymerizable dental restorative composition. The method of treating an oral surface may include providing a dental article and adhering the dental article to an oral (e.g., tooth) surface.
[0213] In other embodiments, the polymerizable dental composition can be hardened into a dental article before application. For example, dental articles such as crowns can be preformed from the hardenable dental compositions described herein. Dental composite articles (e.g., crowns) can be made from the polymerizable dental compositions described herein by casting the composition in contact with a mold and hardening the composition. Alternatively, dental composite articles (e.g., crowns) can be made by first hardening the composition, forming a mill blank, and then mechanically milling the composition into the desired article.
[0214] Another method of treating a dental surface includes providing a polymerizable dental composition as described herein, the composition being in the form of a hardenable, self-supporting, malleable structure having a first semi-finished shape (partially cured), placing the hardenable dental composition on a dental surface in a subject's oral cavity, customizing the shape of the hardenable dental composition, and curing the hardenable dental composition. Customization can be performed in the patient's oral cavity or on a model outside the patient's oral cavity as described in U.S. Patent No. 7,674,850 (Karim et al.), which is incorporated herein by reference.
[0215] Objects and advantages are further illustrated by the following examples, but the particular materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed to unduly limit this invention. All parts and percentages are by weight unless otherwise indicated. EXAMPLES
[0216] Unless otherwise noted, all parts, percentages, ratios, etc. in the examples and the remainder of the specification are by weight. Unless otherwise indicated, all other reagents were obtained or available from fine chemical vendors, such as Sigma-Aldrich Company, St. Louis, Missouri, or may be synthesized by known methods. Table 1 (below) lists the materials used in the examples and their suppliers.
[0217] [Table 3]
[0218] [Table 4]
[0219] Test Method Stress test method (cusp deflection): To measure stress development during the curing process, a rectangular 8x10x15mm aluminium block was machined with a 4x4x8mm groove to accommodate the dental composition to be tested. A linear variable displacement transducer (model GT1000, used with an E309 analogue amplifier, both from RDP Electronics, UK) was positioned as shown to measure the displacement of the cusps as the dental composition was light cured at room temperature. Prior to testing, the aluminium block groove was sandblasted using Rocatec Plus Special Surface Coating Blasting Material (3M), treated with RelyX Ceramic Primer (3M) and finally treated with a dental adhesive, Scotchbond Universal (3M). The groove was completely filled with the example mixture shown in the table, which equated to approximately 100mg of material. The material was irradiated for 1 minute with an Elipar S-10 dental curing light (3M) positioned in near contact (<1mm) with the material in the groove. The cusp displacement (cusp deflection) was then measured in micrometers 9 minutes after the curing light was turned off. Smaller cusp deflection values indicated less polymerization shrinkage stress (PSS) on the surrounding substrate (tooth) during the actual restorative dental procedure.
[0220] Depth of Cure Test (DOC) Method: Cure depth was determined by filling a 10 millimeter stainless steel mold cavity with the composite, covering the top and bottom of the mold with a sheet of polyester film, pressing the sheet to provide a flat composition surface, placing the filled mold on a white background surface, irradiating the dental composition for 10 or 20 seconds as indicated using a dental curing light (3M Dental Products Curing Light Elipar S-10) positioned in near contact (<1 mm) with the material in the channel, separating the polyester film from both sides of the mold, gently removing (by scraping) the material from the bottom of the sample (i.e., the side not irradiated with the dental curing light), and measuring the thickness of material remaining in the mold. The reported depth is the measured cure thickness (in millimeters) divided by two.
[0221] Barcol Hardness Test Method: Uncured composite samples were sandwiched between a sheet of polyester (PET) film and a glass slide in a 2.5 mm or 4 mm thick TEFLON® mold, cured for 10 or 20 seconds as indicated, and cured with an Elipar S-10, 3M dental curing light (3M Corporation). After irradiation, the PET film was removed and the hardness of the samples was measured on both the top and bottom of the mold using a Barber-Coleman Impressor equipped with an indenter (handheld portable hardness tester, model GYZJ 934-1, Barber-Coleman Corporation, Industrial Equipment Division, Rovers Park, IN). The Barcol hardness values of the top and bottom were measured immediately after exposure.
[0222] Diameter Tensile Strength (DTS): DTS was measured by the following procedure. Uncured composite samples were poured into glass tubes approximately 30 mm long and 4 mm in inner diameter. The glass tubes were filled approximately 1 / 2 full and capped with silicone rubber stoppers. The glass tubes were pressurized to approximately 3 kg / cm 2 The specimen was then compressed axially for 5 minutes at a pressure of 1000 mW / cm. While still under pressure, the specimen was subjected to a 1000 mW / cm 2The samples were light cured for 60 seconds by exposure to a dental curing light having a radiant emittance of more than 1000 nm. The glass tube was rotated during curing to ensure even exposure. Approximately 2 mm thick disks were then cut from the glass tube using a Buehler Iso Met 4000 (Illinois Tool Works, Lake Bluff, Illinois, USA) saw. The resulting disks were stored in distilled water at 37° C. for approximately 24 hours before testing. Measurements were performed using a suitable material testing frame (e.g., Instron 5966, Instron, Canton, Massachusetts) equipped with a 10 kilonewton load cell at a crosshead speed of 1 mm / min. Diameter tensile strength was calculated as described in Craig's Restorative Dental Materials, (Ronals L. Sakaguchi and John M. Powers. "Testing of Dental Materials and Biomechanic", Craig's Restorative Dental Materials, thirteenth ed.,
[0286] Elsevier, 2012, p. 86).
[0223] Test Method for Adhesive Shear Bond Strength to Enamel or Dentin: The adhesive shear bond strength to enamel or dentin of the Examples was evaluated by the following procedure.
[0224] Tooth preparation: Bovine incisors free of soft tissue were embedded in circular acrylic discs. The embedded teeth were stored in water in a refrigerator prior to use. In preparation for adhesion testing, the embedded teeth were ground to expose a flat enamel or dentin surface using 120-grit sandpaper mounted on an abrasive wheel. Further grinding and polishing of the tooth surface was performed using 320-grit sandpaper on an abrasive wheel. The teeth were rinsed continuously with water during the grinding process. The polished teeth were stored in deionized water and used for testing within 2 hours after polishing. The teeth were warmed to room temperature (23°C) to 36°C in a 36°C oven prior to use.
[0225] Tooth preparation: A 2.5 mm thick Teflon mold with a hole approximately 4.7 mm in diameter was fixed to the embedded tooth such that the hole in the mold exposed a portion of the adhesively prepared tooth surface (enamel or dentin). The example material was filled into the hole so that it was completely filled but not overfilled, and light cured for 20 seconds to form a "button" that was adhesively attached to the tooth.
[0226] Adhesive Bond Strength Testing: The adhesive strength of the cured test examples was evaluated by mounting the assembly (described above) in a holder secured in the jaws of an INSTRON tester (Instron Corporation, Canton, Massachusetts) with the polished tooth surface oriented parallel to the direction of pulling. A loop of orthodontic wire (0.44 mm diameter) was placed around an example button adjacent to the polished tooth surface. The ends of the orthodontic wire were secured in the pulling jaws of the INSTRON instrument and pulled at a crosshead speed of 2 mm / min, thereby placing the adhesive bond under shear stress. The force at which the bond broke was recorded in kilograms (kg) and this number was converted to force per unit area (in units of MPa) using the known surface area of the button. Each reported value of adhesion to enamel or adhesion to dentin represents the average of 4-5 replicates.
[0227] Synthesis of cyclic imide addition-cleavage monomers General Procedures: All reactions were carried out in round-bottom flasks or glass jars / vials using crude commercially available reagents.
[0228] Instrumentation. Proton nuclear magnetic resonance ( 1 H NMR) spectrum and carbon nuclear magnetic resonance ( 13 C NMR spectra were recorded on a 500 MHz spectrometer.
[0229] Distillation of methyl methacrylate oligomer mixtures.
[0230] [ka]
[0231] A methyl methacrylate oligomer mixture was prepared according to the procedure described in Example 1 of US Patent No. 4,547,323 (Carlson, GM). The mixture was distilled as described in Moad, CL, Moad, G., Rizzardo, E., and Thang, SH Macromolecules, 1996, 29, 7717-7726. The details are as follows:
[0232] A 1 liter (L) round bottom flask equipped with a magnetic stir bar was charged with 500 grams (g) of the methyl methacrylate oligomer mixture. The flask was fitted with a Vigreux column, a condenser, a distribution adapter, and four collection flasks. With stirring, the distillate was placed under vacuum (0.25 mmHg). The oligomer mixture was stirred at room temperature under vacuum until gas evolution (removal of methyl methacrylate monomer) significantly decreased. The distillation pot was then heated to reflux in an oil bath to distill the oligomer mixture under reduced pressure to give the desired dimer.
[0233] Hydrolysis of methyl methacrylate dimer
[0234] [ka]
[0235] This dimer was hydrolyzed to give the diacid 1 as described in Hutson, L., Krstina, J., Moad, G., Morrow, GR, Postma, A., Rizzardo, E., and Thang, SH Macromolecules, 2004, 37, 4441-4452, with details as follows.
[0236] Diacid 1. A 1 L round bottom flask equipped with a magnetic stir bar was charged with deionized (DI) water (302 milliliters (mL)) and potassium hydroxide (90.46 g, 1612 millimoles (mmol)). The mixture was stirred until homogeneous. Methyl methacrylate dimer (120.0 g, 599.3 mmol) was added. The reaction was fitted with a reflux condenser and heated to 90° C. in an oil bath. After 17 hours, the reaction was removed from the oil bath and cooled to room temperature. The reaction solution was acidified to a pH of approximately 0 using concentrated HCl. Upon acidification, a white precipitate formed. The heterogeneous mixture was vacuum filtered and the white solid was quickly washed with DI water (2×50–100 mL). The white solid was then recrystallized from DI water (220 mL). The recrystallized solid was collected via vacuum filtration using a Buchner funnel. The collected solid was then quickly washed with DI water (2 x 50 mL). The solid was further dried under high vacuum to give diacid 1 (86.67 g, 503.4 mmol, 84%) as a fine white solid.
[0237] Preparation of cyclic imide monomers
[0238] [ka]
[0239] Anhydride 2. A 1 L round bottom flask equipped with a magnetic stir bar was charged with diacid 1 (50.00 g, 290.4 mmol), cyclohexane (500 mL), and acetic anhydride (73.30 mL, 79.16 g, 775.4 mmol). The reaction flask was fitted with a Dean-Stark trap and a reflux condenser. With stirring, the reaction was heated to reflux in an oil bath. The solution was refluxed for 2 hours during which time approximately 200 mL of colorless liquid was removed from the Dean-Stark trap. After 2 hours, the reaction was removed from the oil bath and cooled to room temperature. Upon cooling, a white solid precipitated from the solution. The precipitate was collected via vacuum filtration using a Buchner funnel and quickly washed with cyclohexane (75 mL). The white solid was then recrystallized from cyclohexane (400 mL). The recrystallized solid was collected via vacuum filtration using a Buchner funnel and washed with cyclohexane (2 x 75 mL). The solid was further dried under high vacuum to give the anhydride 2 (34.83 g, 225.9 mmol, 78%) as a white crystalline solid.
[0240] Methacrylate-functionalized addition-cleavage cyclic imide monomers (CIMs) CIM-2, CIM-4, and CIM-6 were prepared from the corresponding carboxylic acid-functionalized cyclic imides and glycidyl methacrylate (Table A) (Reaction Scheme 6). Acid-functionalized imides CIM-1, CIM-3, and CIM-5 (Table A) were prepared through condensation of the corresponding amino acids with cyclic anhydrides prepared from methacrylate dimers (Reaction Scheme 5).
[0241] Methacrylate-functionalized addition-cleavage cyclic imide monomers (CIMs) CIM-8 and CIM-10 and acid functional imides CIM-7, CIM-9, and CIM-11 were also prepared similarly to Reaction Scheme 6 utilizing hydroxyl-functional amines, 3-amino-1-propanol, 5-amino-1-pentanol, 3-amino-1,2-propanediol. For some compounds, the hydroxyl group was reacted with 2-isocyanatoethyl methacrylate.
[0242] The structures of the addition-fragmentation cyclic imide monomers that were synthesized are shown in Table A.
[0243] CIM-1. An approximately 40 mL amber glass bottle equipped with a magnetic stir bar was charged with anhydride 2 (15.00 g, 97.30 mmol) and β-alanine (8.668 g, 97.30 mmol). The two solid reagents were mixed well using a wooden applicator. The reaction was sealed with a Teflon-coated plastic cap. With stirring, the mixture was heated to 125° C. in an oil bath. After 4 hours, the reaction was removed from the oil bath, the cap was removed, and the reaction mixture was opened to the atmosphere and allowed to cool to room temperature. The crude product mixture was purified by filtering twice through a plug of silica gel (approximately 4 cm wide x 10 cm high) using a 50:50 mixture of hexane and ethyl acetate as the eluent to give CIM-1 (13.835 g, 61.42 mmol, 63%) as a white solid. 1 1 H NMR analysis was consistent with the desired product.
[0244] CIM-2. A ca. 8 mL amber glass vial equipped with a magnetic stir bar was charged with CIM-1 (2.00 g, 8.879 mmol) and glycidyl methacrylate (1.262 g, 8.878 mmol), along with triphenylantimony (0.0188 g, 0.0532 mmol). The reaction was sealed with a Teflon-coated plastic cap. With stirring, the mixture was heated to 100° C. in an oil bath. After 18 hours, triphenylphosphine (0.0046 g, 0.0178 mmol) was added. The reaction was continued to stir at 100° C. After an additional 9 hours, the reaction was sampled and 1 H NMR analysis was consistent with the desired product as a mixture of isomers. The reaction was cooled to room temperature to give CIM-2 (3.224 g, 8.775 mmol, 99%) as a clear, colorless, viscous oil.
[0245] CIM-3. An approximately 80 mL amber glass bottle equipped with a magnetic stir bar was charged with anhydride 2 (15.00 g, 97.30 mmol) and 6-aminocaproic acid (12.764 g, 97.30 mmol). The two solid reagents were mixed well using a wooden applicator. The reaction was sealed with a Teflon-coated plastic cap. With stirring, the mixture was heated to 125° C. in an oil bath. After 4 hours, the reaction was removed from the oil bath, the cap was removed, and the reaction mixture was opened to the atmosphere and allowed to cool to room temperature. The crude product mixture was purified by filtering twice through a plug of silica gel (approximately 4 cm wide x 10 cm high) using a 50:50 mixture of hexane and ethyl acetate as the eluent for the first filtration and 75:25 hexane and ethyl acetate as the eluent for the second filtration to give CIM-3 (14.606 g, 54.64 mmol, 56%) as a white solid. 1 1 H NMR analysis was consistent with the desired product.
[0246] CIM-4. A approx. 20 mL glass vial equipped with a magnetic stir bar was charged with CIM-3 (2.22 g, 8.305 mmol) and glycidyl methacrylate (1.180 g, 8.301 mmol), along with triphenylantimony (0.0176 g, 0.0498 mmol). The reaction was sealed with a Teflon-coated plastic cap. With stirring, the mixture was heated to 100° C. in an oil bath. After 18 hours, triphenylphosphine (0.0044 g, 0.0166 mmol) was added. The reaction was continued to stir at 100° C. After an additional 9 hours, the reaction was cooled to room temperature and sampled. 1 H NMR analysis revealed a small amount of unreacted epoxide. The reaction was reheated to 100° C. After 6 hours, the reaction was cooled to room temperature and sampled. 1 H NMR analysis revealed a small amount of unreacted epoxide. The reaction was reheated to 100° C. After 23 h, the reaction was cooled to room temperature and sampled. 1H NMR analysis was consistent with the desired product as a mixture of isomers. The reaction afforded CIM-4 (3.359 g, 8.203 mmol, 99%) as a pale yellow viscous oil.
[0247] CIM-5. An approximately 80 mL glass bottle equipped with a magnetic stir bar was charged with anhydride 2 (10.00 g, 64.87 mmol) and 12-aminododecanoic acid (13.968 g, 64.87 mmol). The two solid reagents were mixed well using a wooden applicator. The reaction vessel was then capped with a screw-on vacuum adapter and left open to the atmosphere. With stirring, the mixture was heated to 125° C. in an oil bath. After 50 minutes, the reaction was placed under vacuum (approximately 0.3 mm Hg). After 4 hours, the reaction was removed from the oil bath, the cap was removed, and the reaction mixture was allowed to cool to room temperature open to the atmosphere. The crude product mixture was dissolved in dichloromethane (100 mL) and then vacuum filtered through a Buchner funnel to remove insoluble material. The filtered dichloromethane solution was concentrated in vacuo. The residue was redissolved in a 60:40 mixture of hexane and ethyl acetate and purified by filtering through a plug of silica gel (approximately 4 cm wide x 10 cm high) using a 60:40 mixture of hexane and ethyl acetate as the eluent. The filtered solution was then concentrated in vacuo. The silica gel filtration was repeated two more times to give CIM-5 (11.910 g, 33.89 mmol, 52%) as a clear, colorless, viscous oil. 1 1 H NMR analysis was consistent with the desired product.
[0248] CIM-6. A approx. 20 mL glass vial equipped with a magnetic stir bar was charged with CIM-5 (5.000 g, 14.23 mmol) and glycidyl methacrylate (2.02 g, 14.21 mmol), along with triphenylantimony (0.0301 g, 0.0852 mmol). The reaction was sealed with a Teflon-coated plastic cap. With stirring, the mixture was heated to 100° C. in an oil bath. After 24 hours, triphenylphosphine (0.0075 g, 0.0286 mmol) was added. The reaction was continued to stir at 100° C. After an additional 18 hours, the reaction was sampled and 1H NMR analysis was consistent with the desired product as a mixture of isomers. The reaction was cooled to room temperature to give CIM-6 (7.012 g, 14.20 mmol, 100%) as a viscous yellow oil.
[0249] CIM-7. An approximately 240 mL amber glass bottle with a Teflon covered thread and a magnetic stir bar was charged with anhydride 2 (25.00 g, 162.2 mmol) and then placed in a room temperature water bath. 3-amino-1-propanol (12.3 mL, 12.18 g, 162.2 mmol) was then added over 5 minutes. The bottle was then fitted with a lid adapted to apply a vacuum. The bottle was placed in a 125° C. oil bath and stirred. After 30 minutes at 125° C., the reaction was placed under vacuum. After an additional 4 hours, the reaction was backfilled with nitrogen and cooled to room temperature to give a clear yellow viscous liquid. The reaction was opened to the atmosphere and dissolved in a 90:10 mixture of dichloromethane and ethyl acetate. The crude product mixture was purified by filtering twice through a plug of silica gel (approximately 7.5 cm wide x 15 cm high) using a 90:10 mixture of dichloromethane and ethyl acetate as the eluent. The eluent was concentrated in vacuo to give a colorless oil. The crude product mixture was further purified by filtering two more times through a plug of silica gel (approximately 7.5 cm wide x 15 cm high) using a 90:10 mixture of dichloromethane and ethyl acetate as the eluent for the first filtration and a gradient of a 95:5 to 90:10 mixture of dichloromethane and ethyl acetate as the eluent to give CIM-7 (11.13 g, 52.68 mmol, 32%) as a colorless oil. 1 1 H NMR analysis was consistent with the desired product.
[0250] CIM-8. A 30 mL glass vial equipped with a magnetic stir bar was charged with CIM-7 (3.00 g, 14.2 mmol) and 2-isocyanatoethyl methacrylate (2.01 mL, 2.20 g, 14.2 mmol) and a drop of dibutyltin dilaurate from a pipette tip. The reaction was sealed with a Teflon-coated plastic cap. With stirring, the mixture was heated to 50° C. in an oil bath. After 48 hours, the reaction was sampled and 1 H NMR analysis was consistent with the desired product. The reaction was cooled to room temperature to give CIM-8 (4.946 g, 14.11 mmol, 99%) as a clear, colorless, viscous oil.
[0251] CIM-9. An approximately 240 mL amber glass bottle with Teflon covered threads and a magnetic stir bar was charged with anhydride 2 (25.00 g, 162.2 mmol) and then placed in a room temperature water bath. 5-amino-1-pentanol (17.5 mL, 16.7 g, 162.2 mmol) was then added over 10 minutes. The bottle was placed in a 125° C. oil bath with stirring and open to the atmosphere. After 30 minutes, a lid adapted to apply a vacuum to the bottle was attached and the reaction was placed under vacuum. After an additional 3.5 hours, the reaction was cooled to room temperature and opened to the atmosphere to give a clear yellow sticky material. The reaction was opened to the atmosphere and dissolved in a 90:10 mixture of dichloromethane and ethyl acetate. The crude product mixture was purified by filtering four times through a plug of silica gel (approximately 2.5 cm wide x 12.5 cm high) using a 90:10 mixture of dichloromethane and ethyl acetate as the eluent. After the final silica gel plug filtration, the eluent was concentrated in vacuo to give a colorless viscous oil. This oil was further dried by blowing air through the material using an 18-gauge needle to give CIM-9 (11.91 g, 49.78 mmol, 31%) as a clear, colorless viscous liquid. 1 1 H NMR analysis was consistent with the desired product.
[0252] CIM-10. A 30 mL glass vial equipped with a magnetic stir bar was charged with CIM-9 (5.00 g, 20.9 mmol) and 2-isocyanatoethyl methacrylate (2.95 mL, 3.24 g, 20.9 mmol) and a drop of dibutyltin dilaurate from a pipette tip. The reaction was sealed with a Teflon-coated plastic cap. With stirring, the mixture was heated to 50° C. in an oil bath. After 168 hours, the reaction was sampled and 1 H NMR analysis was consistent with the desired product. The reaction was cooled to room temperature to give CIM-10 (8.199 g, 20.78 mmol, 99%) as a clear, colorless, viscous liquid.
[0253] CIM-11. An approximately 240 mL glass bottle with a Teflon covered thread and equipped with a magnetic stir bar was charged with anhydride 2 (25.00 g, 162.2 mmol) and (+ / -) 3-amino-1,2-propanediol (14.78 g, 162.2 mmol). The bottle was then fitted with a lid adapted to apply a vacuum. The bottle was placed in a 125°C oil bath and stirred. After 15 minutes at 125°C, the reaction was placed under active vacuum. The active vacuum was turned off and the reaction was left under static vacuum for 5 minutes and then briefly returned to active vacuum. This procedure was repeated two more times and then the reaction was left under static vacuum with stirring for 4 hours at 125°C. The reaction was then backfilled with nitrogen and cooled to room temperature to give a yellow / orange glassy solid. The crude reaction product was dissolved in dichloromethane using sonication for 30 minutes. The crude product mixture was then filtered through a plug of silica gel (approximately 12.5 cm wide x 7.5 cm high) using a 97:3 mixture of dichloromethane and methanol as the eluent. The eluent was concentrated in vacuo to give a colorless viscous liquid. The crude product mixture was filtered once more through a plug of silica gel (approximately 12.5 cm wide x 7.5 cm high) using a 95:05 mixture of dichloromethane and methanol as the eluent to give CIM-11 (11.87 g, mmol, 32%) as a colorless oil. 1 1 H NMR analysis was consistent with the desired product.
[0254] AFM1 synthesis:
[0255] [ka]
[0256] AFM1. A 250 mL amber bottle equipped with a magnetic stir bar was charged with glycidyl methacrylate (23.0 mL, 24.8 g, 174 mmol) and triphenylantimony (0.369 g, 1.04 mmol). The reaction was covered with a plastic cap and two 16 gauge needles were pierced through the cap to allow air into the reaction. With stirring, the mixture was heated to 100° C. in an oil bath. Diacid 1 (15.0 g, 87.1 mmol) was added to the reaction in small portions over 1.5 hours. After 21 hours, triphenylphosphine (0.091 g, 0.35 mmol) was added. The reaction was continued to stir at 100° C. After an additional 6.5 hours, the reaction was sampled and 1H NMR analysis was consistent with the desired product as a mixture of isomers and indicated consumption of glycidyl methacrylate. The reaction was cooled to room temperature to give AFM1 as a clear, very pale yellow viscous material.
[0257] [ka]
[0258] Anhydride 2. A 1 L round bottom flask equipped with a magnetic stir bar was charged with diacid 1 (50.00 g, 290.4 mmol), cyclohexane (500 mL), and acetic anhydride (73.30 mL, 79.16 g, 775.4 mmol). The reaction flask was fitted with a Dean-Stark trap and a reflux condenser. With stirring, the reaction was heated to reflux in an oil bath. The solution was refluxed for 2 hours during which time approximately 200 mL of colorless liquid was removed from the Dean-Stark trap. After 2 hours, the reaction was removed from the oil bath and cooled to room temperature. Upon cooling, a white solid precipitated from the solution. The precipitate was collected via vacuum filtration using a Buchner funnel and quickly washed with cyclohexane (75 mL). The white solid was then recrystallized from cyclohexane (400 mL). The recrystallized solid was collected via vacuum filtration using a Buchner funnel and washed with cyclohexane (2 x 75 mL). The solid was dried under reduced pressure to give the anhydride 2 (34.83 g, 225.9 mmol, 78%) as a white crystalline solid.
[0259] Synthesis of bis(cyclic imide) addition-cleavage monomers Preparation of BCIM monomer Bis-cyclic imide monomers (BCIMs) BCIM-1, BCIM-2, and BCIM-3 were prepared with different chain lengths between the cyclic imide ends (Table A). The bis-imide monomers were prepared by cyclization of diacid 1 to anhydride 2 using acetic anhydride. Cyclic anhydride 2 was then condensed with the appropriate diamine to give the bis-cyclic imide monomer (Reaction Scheme 7). The structures of the synthesized addition-cleavage bis-cyclic imide monomers are shown in Table A.
[0260] BCIM-1. An approximately 40 mL glass bottle equipped with a magnetic stir bar was charged with anhydride 2 (34.52 g, 223.92 mmol) and 1,6-diaminohexane (13.02 g, 111.96 mmol). The two solid reagents were mixed well using a wooden applicator. The reaction vessel was then capped with a screw-on vacuum adapter and placed under a nitrogen atmosphere. With stirring, the mixture was heated to 125° C. in an oil bath. After 20 minutes, the reaction was placed under vacuum (approximately 0.3 mm Hg). After an additional 3 hours, the reaction was removed from the oil bath, the cap was removed, and the reaction mixture was opened to the atmosphere and allowed to cool to room temperature. The crude product mixture was dissolved in dichloromethane (75 mL) and filtered through a plug of silica gel (approximately 4 cm wide x 10 cm high) using an 80:20 mixture of hexane and ethyl acetate as the eluent. The filtered solution was concentrated in vacuo. The silica gel filtration was repeated five more times. The product was then dried under high vacuum to give BCIM-1 (8.3594 g, 21.52 mmol, 19.2%) as a white solid. 1 1 H NMR analysis was consistent with the desired product.
[0261] BCIM-2. An approximately 40 mL glass bottle equipped with a magnetic stir bar was charged with anhydride 2 (10.00 g, 64.87 mmol) and 1,8-diaminooctane (4.679 g, 32.43 mmol). The two solid reagents were mixed well using a wooden applicator. The reaction vessel was then capped with a screw-on vacuum adapter. The flask was connected to a high vacuum line but left at atmospheric pressure. With stirring, the mixture was heated to 125° C. in an oil bath. After 35 minutes, the reaction was placed under vacuum (approximately 0.3 mm Hg). After an additional 4 hours, the reaction was removed from the oil bath, the cap was removed, and the reaction mixture was opened to the atmosphere and allowed to cool to room temperature. The crude product mixture was dissolved in dichloromethane (75 mL) and then vacuum filtered through a Buchner funnel to remove insoluble material. The filtered dichloromethane solution was concentrated in vacuo. The residue was redissolved in dichloromethane and purified by filtering through a plug of silica gel (approximately 4 cm wide x 10 cm high) using dichloromethane as the eluent. The filtered solution was then concentrated in vacuo. The silica gel filtration was repeated two more times. The product was then dried under high vacuum and further dried by blowing air through the clear, colorless, viscous liquid. The product solidified on standing to give BCIM-2 (2.6390 g, 6.335 mmol, 19.5%) as a white solid. 1 1 H NMR analysis was consistent with the desired product.
[0262] BCIM-3. An approximately 40 mL glass bottle equipped with a magnetic stir bar was charged with anhydride 2 (10.00 g, 64.87 mmol) and 1,12-diaminododecane (6.4987 g, 32.44 mmol). The two solid reagents were mixed well using a wooden applicator. The reaction vessel was then capped with a screw-on vacuum adapter and placed under a nitrogen atmosphere. With stirring, the mixture was heated to 125° C. in an oil bath. After 50 minutes, the reaction was placed under vacuum (approximately 0.3 mm Hg). After an additional 5 hours, the reaction was removed from the oil bath, the cap was removed, and the reaction mixture was opened to the atmosphere and allowed to cool to room temperature. The crude product mixture was dissolved in dichloromethane (75 mL) and then vacuum filtered through a Buchner funnel to remove insoluble material. The filtered dichloromethane solution was concentrated in vacuo. The residue was redissolved in an 80:20 mixture of hexanes and ethyl acetate and purified by filtering through a plug of silica gel (approximately 4 cm wide x 10 cm high) using an 80:20 mixture of hexanes and ethyl acetate as the eluent. The filtered solution was concentrated in vacuum. The residue was redissolved in dichloromethane and purified by filtering through a plug of silica gel (approximately 4 cm wide x 10 cm high) using dichloromethane as the eluent. The filtered solution was then concentrated in vacuum. The silica gel filtration was repeated once more using dichloromethane as the eluent. The product was then dried under high vacuum and further dried by blowing air through the clear, colorless viscous liquid. BCIM-3 (3.6170 g, 7.652 mmol, 23.6%) was obtained as a clear, colorless viscous liquid. 1 1 H NMR analysis was consistent with the desired product.
[0263] Preparation of hydroxybis-cyclic imide-1 (HBCIM-1) - Reaction Scheme 8 An amber glass bottle equipped with a magnetic stir bar is charged with 3,3-dimethyl-5-methylene-tetrahydropyran-2,6-dione (anhydride 2) and 1,3-diamino-2-propanol (0.5 equivalents of anhydride 2). The two components are mixed well using a wooden applicator. The bottle is then sealed with a Teflon-coated plastic cap. With stirring, the mixture is heated to 125° C. in an oil bath. After 4 hours, the reaction is removed from the oil bath, the cap is removed, and the reaction mixture is opened to the atmosphere and allowed to cool to room temperature. The crude product mixture is then purified by filtering twice through a plug of silica gel (approximately 4 centimeters wide by 10 centimeters high) using a 50:50 mixture of hexane and ethyl acetate as the eluent to give the desired hydroxy bis-cyclic imide product HBCIM-1.
[0264] Preparation of methacrylated hydroxybis-cyclic imide-1 (MA-BCIM-1) - Reaction Scheme 9 In a glass jar, place HBCIM-1 and 1 equivalent of IEM. These ingredients are mixed by hand using a wooden applicator. BHT (400 parts per million based on the total contents of the jar) and dibutyltin dilaurate catalyst (DBTDL, 0.5 wt%) are then added to the jar, followed by hand mixing. The jar is left at room temperature for 30 minutes, with hand mixing every 10 minutes. The jar is then placed in a 60°C oven for 1 hour, with the ingredients being hand mixed every 10-15 minutes to obtain the desired product, MA-BCIM-1.
[0265] Preparation of General Dental Example Formulations: Resin samples were made by combining all ingredients and heating (at 50° C.) until the solids were completely dissolved (approximately 90 minutes). Subsequent dental paste examples using stock resins were prepared by adding the raw materials to a 40 gram DAC cup, followed by mixing in a speed mixer (Model DAC150 FVZ SpeedMixer, manufactured by FlackTek, Inc., Landrum, South Carolina) at 2500 rpm for 30 second intervals until the materials were combined as indicated by a smooth, homogenous composition. Examples containing only AFM1 and no amount of CIM or BCIM are comparative examples.
[0266] [Table 5]
[0267] [Table 6]
[0268] [Table 7]
[0269] [Table 8]
[0270] [Table 9]
[0271] [Table 10] nm = not measured
[0272] [Table 11] nm = not measured
[0273]
Table 12
[0274]
Table 13
[0275]
Table 14
[0276]
Table 15
[0277]
Table 16
[0278]
Table 17
[0279]
Table 18
[0280]
Table 19
[0281]
Table 20
[0282]
Table 21
[0283]
Table 22
[0284] All cited references, patents, and patent applications in the above application for Letters Patent are incorporated herein by reference in their entirety in a consistent manner. In the event of any inconsistency or contradiction between any portion of the incorporated reference and this application, the information in the foregoing description shall prevail. The foregoing description, given to enable one skilled in the art to practice the claimed disclosure, is not intended to be construed as limiting the scope of the present disclosure, which is defined by the claims and all equivalents thereof. Examples of embodiments of the present invention are listed in the following items [Aspect 1] to [Aspect 35]. [Aspect 1] 1. A dental composition comprising: at least one monomer containing at least two ethylenically unsaturated groups; and an addition-cleavage agent comprising at least one cyclic imide monomer containing an α,β-unsaturated carbonyl. [Aspect 2] The dental composition of embodiment 1, wherein the cyclic imide monomer comprises an imide group and the α,β-unsaturated carbonyl in a heterocycle, the ring comprising at least six covalently bonded atoms. [Aspect 3] 3. The dental composition of embodiment 2, wherein the cyclic imide monomer further comprises a γ-quaternary carbon atom. [Aspect 4] The cyclic imide monomer has the structure: [ka] having where L is a covalent bond or an organic linking group; Y is an alkyl, aryl, hydroxyl, carboxylic acid, or an ethylenically unsaturated polymerizable group; R 1 and R 2 The dental composition according to any one of aspects 1 to 3, wherein are independently an alkyl group. [Aspect 5] R 1 and R 2 is a substituent such that the cyclic imide monomer is ring-opened during polymerization. [Aspect 6] R 1 and R 2 are independently a C1 to C18 alkyl group. [Aspect 7] A dental composition according to any one of Aspects 3 to 6, wherein L is (hetero)alkylene or (hetero)arylene. [Aspect 8] The dental composition according to any one of aspects 3 to 7, wherein Y is a carboxylic acid group or a (meth)acrylate group. [Aspect 9] The dental composition of any one of aspects 3 to 8, wherein L comprises at least one hydroxyl group. [Aspect 10] 3. The dental composition of claim 1 or 2, wherein the cyclic imide monomer comprises at least two cyclic imide groups. [Aspect 11] The cyclic imide monomer has the structure:
change
change
[0039] The dental composition of embodiment 30, wherein the inorganic oxide filler comprises silica, zirconia, or a mixture thereof. [Aspect 32] 32. The dental composition of embodiment 30 or 31, wherein the inorganic oxide filler comprises nanoparticles. [Aspect 33] 33. The dental composition of embodiment 32, wherein the inorganic nanoparticles are in the form of nanoclusters. [Aspect 34] 1. A method of treating a dental surface, the method comprising: Providing a dental composition according to any one of aspects 1 to 33; placing the dental composition on a tooth surface in the oral cavity of a subject; and curing the dental composition. [Aspect 35] 1. A composition comprising: at least one monomer containing at least two ethylenically unsaturated groups; and an addition-cleavage agent comprising at least one cyclic imide monomer containing an α,β-unsaturated carbonyl.
Claims
1. 1. A dental composition comprising: at least one monomer containing at least two ethylenically unsaturated groups; an addition-cleavage agent comprising at least one cyclic imide monomer containing an α,β-unsaturated carbonyl; The cyclic imide monomer has the structure: 【Chemistry 1】 having where L is a covalent bond or an organic linking group; Y is an alkyl, aryl, hydroxyl, carboxylic acid, or an ethylenically unsaturated polymerizable group; R 1 and R 2 are independently an alkyl group; or The cyclic imide monomer comprises at least two cyclic imide groups; The cyclic imide monomer has the structure: 【Chemistry 2】 having where R is an organic linking group; R 1 and R 2 is independently an alkyl group.
2. 2. The dental composition of claim 1, wherein the cyclic imide monomer comprises an imide group and the α,β-unsaturated carbonyl in a heterocycle, the ring comprising at least six covalently bonded atoms.
3. The dental composition of claim 2 , wherein the cyclic imide monomer further comprises a γ-quaternary carbon atom.
4. Formula: 【Chemistry 3】 and a second addition-cleavage agent having the formula: In the formula, R 1 , R 2 , and R 3 are each independently m -Q-, a (hetero)alkyl group, or a (hetero)aryl group, provided that R 1 , R 2 , and R 3 At least one of m -Q-, Q is a linking group having a valence of m+1; Z is an ethylenically unsaturated polymerizable group; m is 1 to 6; each X 1 are independently -O- or -NR 4 -, wherein R 4 is H or C 1 ~C 4 is alkyl, The dental composition according to any one of claims 1 to 3, wherein n is 0 or 1.
5. 4. The dental composition of claim 1, further comprising at least one (meth)acrylate monomer selected from ethoxylated bisphenol A dimethacrylate (BisEMA6), 2-hydroxyethyl methacrylate (HEMA), bisphenol A diglycidyl dimethacrylate (bisGMA), urethane dimethacrylate (UDMA), triethylene glycol dimethacrylate (TEGDMA), glycerol dimethacrylate (GDMA), ethylene glycol dimethacrylate, neopentyl glycol dimethacrylate (NPGDMA), polyethylene glycol dimethacrylate (PEGDMMA), and mixtures thereof.
Citation Information
Patent Citations
Thermoplastic resin composition
JP1995196867A
Additional cleavage agent
JP2014513154A
Imide addition-fragmentation agents
WO2022096973A1
Adhesives comprising cyclic imide addition-fragmentation and adhesion agents
WO2023105327A1